Advanced geological prediction in tunnels based on delay blasting: Wavefield separation mechanism and VMD-HHT-FK joint denoising - Qinliang Sun; Yonglin Li; Dong Hu; Songnan Ru; Shuai Cheng; Xingang Zhang (Tunnelling and Underground Space Technology, 2027)

Disruption of retinol saturase enhances Polyunsaturated Fatty Acid (PUFA) biosynthesis in grass carp (Ctenopharyngodon idella) via upregulation of fads2 - Ru Zhang; Ran Yang; Jiang Zeng; Xiao Xiao; Houpeng Wang; Yongming Li; Xiaosi Wang; Jian Gao; Mudan He; Yonghua Sun (Aquaculture, 2027)

Paternal vitamin D deficiency is associated with offspring testicular developmental abnormalities, fibrosis, and altered sperm miRNA profiles - Yu-Ming Chen; Zhi-Hong Tian; Shi-Yuan Li; Juan Dai; Xing-Ru Wang; Guo-Ying Sun; Min Liu; Berthold Hocher; Mei Tian (Molecular Biology Reports, 2026)

Modeling and control system design of compound rankine cycle-based space reactor system - Jiacheng Zhang; Xinhui Sui; Leilei Qiu; Ru Zhang; Peiwei Sun; Xinyu Wei (Annals of Nuclear Energy, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Phylogenomics of Tanypodinae (Diptera: Chironomidae) redefines relationships in Procladiini and Tanypodini and supports a new tribe - Xiu-Ru Xiao; Yi-Ni Zhang; Hai-Feng Xu; Zhi-Chao Zhang; Yu-Yi Jiang; Yan-Xin Chen; Chen-Hong Li; Bing-Jiao Sun; Fabio Laurindo da Silva; Xiao-Long Lin (Molecular Phylogenetics and Evolution, 2026)

Comprehensive low-damage mechanical weeding technology considering the spatial distribution of crop roots: A case study of maize farmland - Deng Sun; Longzhe Quan; Zhaoxia Lou; Guoxiang Zhang; Chen Ru; Xiaojie Li; Zhiming Guo; Jinbin He; Chuan Wang; Yongheng Wang (Computers and Electronics in Agriculture, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

From coal gasification slag-derived water glass to monodisperse silica sol: Silicate-species evolution and particle-growth mechanisms - Ru Guo; Jianbo Zhang; Yiyang Li; Hongxiang Xu; Zhengping Zuo; Zhiming Sun; Shaopeng Li; Huiquan Li (Journal of Environmental Chemical Engineering, 2026)

Deep learning-based decoupling of hydro-meteorological signals from Cheonji caldera lake water levels for volcanic precursor detection - Eu-ru Lee; Sung-Hwan Park; Won-Kyung Baek; Hyung-Sup Jung; Ha-Seong Lee; Sun-Cheon Park (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Pickering emulsion stabilized by whey protein isolate and psyllium husk powder: Interface properties and stabilization mechanism - Huifang Liu; Ru Tian; Yinshi Sun; Shuang Jiang; Di Qu (Food Chemistry, 2026)

pH-responsive microcapsules co-delivering radioprotectant and probiotics for synergistic mitigation of radiation-induced enteritis - Caifang Gao; Jiaxuan Ma; Luke Ge; Yongle Zhao; Ru Feng; Pengqi Zhu; Jinghua Sun; Ruiping Zhang (Chemical Engineering Journal, 2026)

Intracellular imaging and therapeutic application of liver fibrosis via a microRNA-on self-stacking amplification circuit - Xiao-Meng Sun; Yin-Xiang Chen; Lin-Ru Xu; Rui Bai; Li-Zeng Zhu; Gaoxiang Ma; Lian-Wen Qi; Yu Gu; Qun Liu (Analytica Chimica Acta, 2026)

Complete mitochondrial genomes and phylogenetic analysis of three species of Indo-Pacific freshwater gobies, Stiphodon (Gobiiformes, Oxudercidae) - Cheng-He Sun; Xian-Ru Li; Su-Fan Zhou; Yan-Zi Zhong; Xiao Ma; Xiao-Die Chen (Journal of Genetics, 2026)

Novel attenuating intestinal oxidative stress strategy: Selenium nanoparticles combined with curcumin impeding the endoplasmic reticulum stress & apoptotic pathways - Ze-yuan Sun; Ling Lu; Si-nian Li; Rui-chao Li; Ling-qing Kong; Ru-nan Zuo (PharmaNutrition, 2026)

Quercetin restores oocyte maturation and embryo development in DEHP-exposed mice via mitochondrial protection and apoptosis inhibition - Dui Sun; Qi Yang; Zhi-Hui Gong; Meng-Lei Feng; Zhi-Wen Jia; Bin-Shuo Yang; Zhao-Yu Jiang; Chun-Ru Song; Fang-Rui Xue; Xiao-Jie Zhang; Hao-Yang Zhang; Chun-Lan Zhang; et al. (Chemico-Biological Interactions, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Mechanical degradation mechanisms of colorful clay subjected to dry-wet cycling - Yin-Lei Sun; Qing-Ru Du; Xin-Yao Yang; Wei Luo; Xiang Qian; Xian-Wei Zhang (Transportation Geotechnics, 2026)

Paedocin A: An undescribed iridoid with a C1-C4 ether linkage from Paederia foetida with hepatoprotective effects - Wan-Qi Zhang; Xin-Yue Li; Ming-Hui Sun; Jie Zhou; Guo-Ru Shi; De-Quan Yu; Yan-Fei Liu (Phytochemistry Letters, 2026)

Phytohormonal orchestration of plant phosphate starvation responses - Kai-Kai Lu; Ru-Feng Song; Yu-Pu Fan; Ling-Yu Xu; Bo-Hao Chen; Shu-Xian Li; Meng-Tian Sun; Guo-Mao Liu; Xiao-Li Huang; Lin Li; Xin-Ru Guo; Feng Ren; et al. (Journal of Plant Physiology, 2026)

The SP1/NEDD4L Axis Suppresses the Breast Cancer Progression by Downregulating SNAI2 Expression - Baile Zuo; Xiaoyan Li; Mengke Wang; Zhuoya Yin; Yifan Guo; Liping Zhao; Ru Yang; Binghua Tong; Zhenni Guo; Meiqing Sun; Jin Zhao; Huina Zhang; et al. (Biochemical Genetics, 2026)

TRMT10A maintains lipid homeostasis independently of its tRNA m1G9 methyltransferase activity - Huihui Sun; Yu Wang; Shanpeng Liu; Yan Jin; Jianyang Ge; Bowen Zhang; Yongteng Wang; Weifeng Sun; Yun Bai; Yuyong Tao; Yi Lu; Ru-Juan Liu; et al. (Science China Life Sciences, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

FOXG1 Transcriptionally Orchestrates Parvalbumin+ Interneuron Function Contributing to Schizophrenia Pathology - Pengfei Jiang; Mingzhao Su; Xue Zhou; Baoshen Zhang; Jie Sun; Ru Ba; Junhua Liu; Chunjie Zhao (Neuroscience Bulletin, 2026)
Schizophrenia (SCZ) is characterized by heterogeneous symptoms including abnormal perception, social withdrawal, and cognitive deficits. Parvalbumin-positive (PV + ) interneurons are particularly vulnerable in SCZ; however, the underlying cellular basis remains unclear. In this study, we found that selective deletion of the SCZ risk gene Foxg1 in PV + interneurons of mice recapitulated aspects of the disease phenotype, including impaired sensorimotor gating, anxiety-like behavior, social deficits, and cognitive impairments. Foxg1 deficiency caused dendritic simplification, reduced spine density, and impaired synaptic transmission in PV + interneurons of the prelimbic cortex. Our findings indicate that FOXG1 directly drives a set of SCZ risk genes that encode synaptic receptors, adhesion molecules, scaffolding proteins, transporters, ion channels, and vesicle-trafficking proteins, thereby orchestrating PV + interneuron synaptic function. Notably, FOXG1 activates the transcription of metabotropic glutamate receptor 3 (mGluR3), and pharmacological potentiation of mGluR3 activity alleviates behavioral deficits in Foxg1 conditional knockout mice. In conclusion, our findings identify a novel role for Foxg1 in PV + interneurons, providing new mechanistic insights into their vulnerability to SCZ.

Regionally specific dysregulation of gut microbiota and host–metabolite interface in podophyllotoxin-induced enterotoxicity based on the toxicological evidence chain concept - Tao Jiang; Jiaxing Sun; Chuanxin Liu; Yuhan Sun; Hetao Chen; Dongxia Liu; Ruyan Chen; Yanqiu Wang; Yi Ru; Jiajia Duan (Toxicology and Applied Pharmacology, 2026)

Deep carbon cycling in continental subduction zones - Sheng-Ao Liu; Wan-Yu Sun; Yuan-Ru Qu; Hong-Li Yang (Lithos, 2026)

Dual-engineered defect-rich molecularly imprinted zirconium metal organic framework platform for selective adsorption and ultrasensitive analysis of alternariol - Shi-Rong Sun; Lu Liu; Xia Wang; Yan Dong; Yan Li; Qianyun Sun; Yanfang Zhao; Xiangfeng Chen; Yong-Ning Wu; Rabah Boukherroub; Ru-Song Zhao (Journal of Hazardous Materials, 2026)

Numerical and experimental study on the soot formation in methane multi-jet flames under microgravity - Wen-Jiao Wang; Kai-Ru Jin; Zhi-Hao Zheng; Hong-Qing Shi; Du Wang; Ling-Nan Wu; Ya-Wen Liu; Longfei Li; Jiayu Sun; Yu Cheng Liu; Zhen-Yu Tian (Fuel, 2026)

Effects of salinity and fermentation time on the microbial community, flavor, and metabolites of shrimp paste - Jing-ru Chen; Jia-bo Huang; Jing Li; Shi-meng Sun; Peng-fei Jiang (Food Research International, 2026)

Calcium-promoting peptide IWGR and EIY: Targeted screening based on the calcium-sensing receptor (CaSR), validation through in situ single-pass intestinal perfusion (SPIP), and analysis of calcium-promoting characteristics - Hongli Zhi; Xiaomin Liu; Xinmiao Sun; Jingjing Ru; Shan Gao; Huiping Liu; Xiaowei Zhang (Food Chemistry, 2026)

Bioactive PVA/SDES propolis extracts composite films for extending oyster shelf life: Structure, functionality, and preservation performance - Tian Du; Lin-Kun Sun; Pei-Ru Zhou; Yu-Cang Zhang; Yan-Zhen Zheng (Food Packaging and Shelf Life, 2026)

Knowledge-infused hierarchical causal inference framework for decoding sludge settleability to quantitatively regulate multi-process wastewater treatment - Yucheng Li; Chen Cai; Feiyun Sun; Xiangfeng Huang; Kaiming Peng; Ru Guo; Jia Liu (Bioresource Technology, 2026)

Danaeopsis Heer ex Schimper (Marattialean fern) from the upper Middle Triassic of Ordos Basin, North China and a review of the genus - Yanqi Sun; Shenghui Deng; Yuanzheng Lu; Ru Fan; Dan Lyu; Songyan Liu (Review of Palaeobotany and Palynology, 2026)

The OsMYB60–OsGL1-11 module regulates drought tolerance in rice - Ru Li; Jinliang Sun; Fuping Chen; Xuemei Qin; Tianmin Ouyang; Weijian Cen; Jijing Luo (Plant Science, 2026)

Mechanisms of flow-induced noise and control in underwater grille-cavity systems: Effects of grille number and inclination - Qing-Shuang Zhang; Yong-Liang Xiong; Ru-Nan Hua; Guo-Cang Sun; Dan Yang (Ocean Engineering, 2026)

Multifunctional carboxymethyl cellulose/polydopamine dual-network conductive hydrogels for motion detection and photothermal therapy - Yiying Wei; Bo Cong; Xiaopu Ji; Dangyang Wang; Jinghui Hu; Zonglei Mou; Haiqing Song; Yue Zhi; Yushu Liu; Guofeng Zhang; Wan Ru Sun; Pingyu Wang; et al. (Carbohydrate Polymers, 2026)

Editor's note “Silica nanoparticles promoted pro-inflammatory macrophage and foam cell transformation via ROS/PPAR/NF-B signaling” [Sci. Total Enviro. 881 (2023) 163430] - Caixia Guo; Xinying Zhao; Ru Ma; Lingnan Zhu; Yueyue Chen; Zhiwei Sun; Yanbo Li (Science of The Total Environment, 2026)

Cissatriterpenoids D-L, nine undescribed polyhydroxylated oleanane triterpenoids from Cissampelos pareira var. hirsuta - Shuang-Qin Cao; Ru-Yi Pan; Tong-Tong Zhang; Jian-Hong Gong; Meng Li; Hui Chen; Jing-Ke Zhang; Zhi-You Hao; Xiao-Ke Zheng; Yan-Jun Sun; Wei-Sheng Feng (Phytochemistry, 2026)

Co-gasification coupled with steam reforming of inseparable livestock biowastes for green hydrogen-rich syngas production - Jiarui Zhu; Qiuhan Pu; Liang Wang; Ge Kong; Zengjian Guo; Ru Sun; Guanyu Zhang; Xin Zhang; Xuesong Zhang; Lujia Han (Journal of Environmental Chemical Engineering, 2026)

From biomass to supercapacitor electrode materials: bamboo derived carbon decorated with MnO2 used in flexible energy storage device - Pengfei Jia; Binyang Liu; Shenao Li; Yizhan Sun; Shuwen Lv; Ru Liu; Yuandong Xu; Xia Zhang; Wei Kong Pang; Peng Li (Fuel, 2026)

Identification of key factors influencing monthly runoff simulation through the integration of deep learning and physically-based hydrological models - Jiyu Zhang; Yufeng Wang; Liangjie Zhao; Ru Sun; Jiayu Sun; Shufei Wang; Shiqin Xu; Zhe Yang (Environmental Modelling & Software, 2026)

Dual-functional eggshell-derived system for comprehensive phosphorus recovery from agricultural wastewater: From laboratory validation to pilot-scale implementation - Qiao Wu; Maoqing Fan; Xiaoyu Zheng; Ming Zeng; Saihong Ru; Chengyou Sun; Chao Huang (Bioresource Technology, 2026)

Studies on secondary metabolites and anti-inflammatory activity of fungus Penicillium citreosulfuratum YFC-1 from Sphagneticola trilobata - Zhao-xia Chen; Wen-xing Li; Ru-tong Chen; Yang Hui; Zhen-fan Sun; Wen-hao Chen (Natural Product Research, 2026)

Causal-informed domain adaptation with cross-attention for predicting anomalous effluent quality fluctuations in wastewater treatment plants - Hanxin Zhang; Haiping Zhang; Jia Liu; Kaiming Peng; Ru Guo; Feiyun Sun; Xiangfeng Huang; Chen Cai (Water Research, 2026)

The role of artificial intelligence in advancing population-based cancer registration - Shuai Ding; Mingyuan Liu; Hao Wang; Cheng Song; Luyue Zhao; Zhihao Yang; Yue Wang; Yifan Wang; Haitao Cui; Zihao Liu; Dongrun Liu; Tomohiro Matsuda; et al. (Science Bulletin, 2026)

Cyclopentanoid monoterpene glycosides from the aerial parts of Paederia foetida L - Wan-Qi Zhang; Xin-Yue Li; Ming-Hui Sun; Jie Zhou; Guo-Ru Shi; De-Quan Yu; Yan-Fei Liu (Phytochemistry, 2026)

Exploratory analysis of epigenetic dynamics and small extracellular vesicles in Penaeus vannamei hemocytes under inactivated Vibrio parahaemolyticus priming - Yu-Ru Lin; Guan-Lin Lai; Yu-Hsuan Sun; Ta-Jeng Yang; Ting-Yu Huang; Huu-The Nguyen; Muhammad Ar Rozzaaq Nugraha; Novi Rosmala Dewi; Yeh-Fang Hu; Fan-Hua Nan (Journal of Invertebrate Pathology, 2026)

Grape seed extract incorporated into konjac glucomannan-based batter inhibits acrylamide and advanced glycation end products in fried fish nuggets - Runlin Wu; Jingwen Sun; Xia Mou; Shanbai Xiong; Ru Liu (Food Chemistry, 2026)

GaAs/GaN-based self-powered catalytic systems driven by tribovoltaic effect enable efficient degradation of azo dyes - Meng-Nan Liu; Yan-Xin Wu; Yu-Tong Sun; Xu Li; Ru Li; Jun Zhang; Yun-Ze Long (Chemical Engineering Journal, 2026)

Coconut shell pyrolysis oil: dual-pathway approach to antioxidants and renewable aromatic biofuels - Ru Sun; Jincheng Zhang; Meng Sun; Xinghua Liu; Dan Qian; Ping Huang (Fuel, 2026)

Construction of acyl-homoserine lactone-producing engineered bacteria for activating low-temperature anammox process - Jiangwei Wang; Jianhang Zhou; Yiming Feng; Jingqi Sun; Ru Zheng; Kuo Zhang; Juejun Pan; Xiaogang Wu; Liguo Zhang; Sitong Liu (Environmental Research, 2026)

Side-chain modified covalent organic frameworks for enhanced visible light photocatalytic degradation of bisphenol A and application in seawater - Tianshuo Liu; Jing Sun; Meng Xie; Ru-Song Zhao (Chemical Engineering Journal, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Online state estimation of steam generator based on extended Kalman filter - Leilei Qiu; YuLong Wang; JiaCheng Zhang; Ru Zhang; Gang Luo; Peiwei Sun; Xinyu Wei (Annals of Nuclear Energy, 2026)

Experimental study on the enhanced separation performance of a vertical corrugated plate dryer under acoustic agglomeration - Tuo Wang; Siqin Hou; Mingyang Sun; Zerun Zhang; Pei Luo; Lei Jiang; Ru Li; Guoqing Shen; Rulei Sun (Annals of Nuclear Energy, 2026)

Optimizing the spatial configuration of scallop suspended cultivation net cages by leveraging seston flux variables based on the lattice Boltzmann hydrodynamics - Gangqin Tu; Haifei Liu; Zhiming Ru; Tao Sun; Wei Yang; Wei Huang; Li Cheng (Aquaculture, 2026)

OsPP2C03 positively regulates rice drought stress resistance through a non-canonical ABA pathway - Yao Wang; Mingxin Chen; Di Wu; Ru Li; Hanxing Wei; Lingwen Meng; Xuemei Qin; Jinliang Sun; Tianmin Ouyang; Weijian Cen; Rongbai Li; Jijing Luo (Plant Science, 2026)

Biofilm-mediated mitigation of nitrous oxide emissions in anammox-based wastewater treatment - Zhiman Lin; Jinfan Zhang; Ru Wang; Jingmin Ou; He Zhang; Zihua Wang; Fangyuan Zheng; Xiantao Sun; Xin Wei; Yiming Huang; Zhenguo Chen; Mark C.M. van Loosdrecht; et al. (International Biodeterioration & Biodegradation, 2026)

Longitudinal monitoring of global prevalence, genomic characterization and transmission routes of Salmonella Derby strains from food, humans and the environment - Min-Ge Wang; Dong-Xiao Ru; Ying-Xin Ruan; Ying Chu; Peng-Yu Zhang; Sheng Chen; Ruan-Yang Sun (Food Research International, 2026)

Sustainable extraction and bioconversion of tea stems using NADES: Dual benefits in polyphenolic recovery and carbohydrates enzymatic hydrolysis - Lin-Kun Sun; Pei-Ru Zhou; Tian Du; Yu-Cang Zhang; Yan-Zhen Zheng (Food Chemistry, 2026)

Synergistic microbial co-culture of Saccharomyces cerevisiae and Clostridium kluyveri enhances ethyl hexanoate production for stable flavor synthesis in strong-flavor Baijiu - Qiumei Zhang; Ru Zhang; Xi Chen; Meiyue Han; Ya Zhang; Weiwei Li; Xiuting Li; Jianxiong Hao; Baoguo Sun (Food Bioscience, 2026)

Quantitative resolution analysis in seismic imaging: From classical theory to cutting-edge advances - Jidong Yang; Jianping Huang; Hejun Zhu; Jiaxing Sun; Li-yun Fu; George McMechan; Houzhu Zhang; Ru-Shan Wu (Earth-Science Reviews, 2026)

Overlooked Roles of Pharmaceutical Metabolic Products in Stimulating Microbial Metabolism and Antibiotic Resistance Gene Dissemination of Anaerobic Sludge - Jing Wu; Dan Sun; Yuan Pan; Dong‐Feng Liu; Hui Zhang; Jun‐Hua Zhou; Tong Gao; Jie Wu; Ru‐Li He; Yin‐Guang Chen; Wen‐Wei Li (Environmental Microbiology, 2026)
The roles of non‐antibiotic pharmaceuticals in shaping the dissemination behaviours of antibiotic resistance genes (ARGs) in wastewater treatment systems remain poorly understood, and the influences of their transformation products have been overlooked. Here, we unveil more profound impacts of the metformin (MET) biotransformation product than the parent pollutant on the microbial community structure and ARG propagation of wastewater anaerobic sludge. The exposure to MET and its metabolic products guanylurea (GUA) at environmentally relevant concentrations both raised the methane production and resulted in up to 52.5% higher sludge ARGs abundance relative to the unexposed control. Especially, the GUA group showed up to 188‐fold upregulation in several ARGs including bcrA , PmrF , acrB and mexF , enabled 3218‐fold enrichment of plasmids from several bacteria. The underlying mechanisms were elucidated by integrated metagenomics, molecular dynamics simulations, and metabolic profiling analyses. MET and GUA were found to trigger coordinated cellular responses including disrupted glycerophospholipid metabolism, increased membrane permeability and broad metabolic reprogramming, which collectively boosted the ARGs dissemination. Overall, this work establishes a mechanistic link between micropollutant‐induced microbial stress and ARGs propagation in anaerobic sludge, and advocates for re‐evaluating the environmental risks of non‐antibiotic pharmaceuticals and integrating resistance control into wastewater management framework.

An oocyte and yolk syncytial layer-derived Nanog-cyp11a1-pregnenolone axis promotes extraembryonic development - Ru Zhang; Shengbo Jiao; Mudan He; Wenyuan Li; Houpeng Wang; Ding Ye; Zuoyan Zhu; Yonghua Sun (Science Bulletin, 2025)

Assessing the atmospheric deposition of inorganic nitrogen and phosphorus over the Yellow Sea - Limin Yu; Ru Li; Chong Zhang; Hao Sun; Zhe Zhang; Pengfei Zhao; Pengji Zhang; Fan Yang (Regional Studies in Marine Science, 2025)

Natural and built environments and heart failure risk: An exposome-wide analysis in the UK Biobank - Xuewei Huang; Siyu Yin; Meng Yao; Fang Lei; Weifang Liu; Lijin Lin; Tao Sun; Yuanyuan Cao; Xingyuan Zhang; Ru Li; Liwen Wang; Yufeng Hu; et al. (Environmental Research, 2025)

Unveiling the 3D Li2S nucleation mechanism through ultra-small Ru engineering on MoS2 for high-efficiency Li S batteries - Mengjing Jin; Rui Wang; Shimin Wang; Ru Chen; Jiayue Li; Yanchun Wang; Renqian Tao; Guowen Sun; Jinyuan Zhou; Xiaojun Pan (Chemical Engineering Journal, 2025)

A Transformer-based framework with generative spectral augmentation for online monitoring of hyaluronic acid fermentation - Weilu Tian; Lixuan Zang; Yunyi Li; Cheng Peng; Jinhua Zhang; Huarong Shao; Ruiqing Xian; Ru Sun; Fei Liu; Haining Tan; Peixue Ling (Carbohydrate Polymers, 2025)

DPP4, a potential tumor biomarker, and tumor therapeutic target: review - Lu Sun; Yuhui Ma; Chenchen Geng; Xiaoqian Gao; Xinbing Li; Qi Ru; Shuzhen Zhu; Ping Zhang (Molecular Biology Reports, 2025)

Characterization of the complete mitogenomes of Synodontis decorus and Synodontis petricola (Teleostei: Mochokidae) with a phylogenetic analysis of the Mochokidae family - Cheng-He Sun; Xian-Ru Li; Yi-Jing Zhan; Chang-Hu Lu (Molecular Genetics and Genomics, 2025)

Complete mitochondrial genome sequence of Nannostomus eques and comparative analysis with Nannostomus beckfordi - Xian-Ru Li; Cheng-He Sun; Yi-Jing Zhan; Shuang-Xi Jia; Chang-Hu Lu (Molecular Genetics and Genomics, 2025)

Transcriptome analysis reveals no obvious unintended effects in the spleen of CRISPR/Cas9-mediated CD163 and pAPN double-knockout pigs - Zhi-Guo Liu; Nan Wang; Wan-Jie Wang; Lei Huang; Shun-Shun Chi; Yu-Xin Nie; Mao-Sha Yuan; Ya-Ru Sun; Yu-Lian Mu; Kui Li (Functional & Integrative Genomics, 2025)

Elucidating the impact of salt concentration on volatile flavor profiles and microbial dynamics in fermented cockle paste using GC-IMS and high-throughput 16S rDNA sequencing - Shi-meng Sun; Jia-bo Huang; Jing Li; Jing-ru Chen; Peng-fei Jiang (Food Research International, 2025)

Underwater-adhesive and mechanically reinforced porous amidoxime hydrogel for fast and selective uranium extraction from seawater - Xue Bai; Pan Wang; Ru Feng; Jianming Pan; Yonghui Sun (Desalination, 2025)

SiO2 aerogel-encapsulated and multilayer carbon-magnetic heterostructure-reinforced carbon felt for high-efficiency EM wave absorption and thermal insulation - Xinying He; Hanxu Jia; LiFen He; Ru Wang; Wei Ye; Qilong Sun; Xiaoyun Long (Chemical Engineering Journal, 2025)

The new ten-numbered macrolide, diaporthsin L, from endophytic fungus Diaporthe sp. G-4 isolated from Strobilanthes cusia (Nees) Kuntze - Jun-yi Li; Zhen-xian Cun; Hui-hui Sun; Jie-Zheng Shi; Wen-xiang Yan; Jun-meng Xia; Dong Gan; Mao-ru Li; Ju-cheng Zhang; Zhong-tao Ding (Natural Product Research, 2025)

Salicylic acid promotes arsenic uptake in Pteris vittata via regulation of key genes and elevated nitric oxide and spermidine - Zhi-Hua Dai; Ze-Chao Li; Xi Chen; Ru Huang; Jian-Hua Sun; Chen-Jing Liu; Lena Q. Ma; Ru-Yi Yang (Journal of Hazardous Materials, 2025)

LSPR-enhanced hydrogen evolution via Au-UiO-67-NH2/ZnIn2S4/MoS2 hybrid nanostructures - Jing Ru; Kang Li; Guofeng Sun; Maoxia Chen; Yu Hu; Zhiguo Wen; Dongyu Wu; Xuan Yi; Zhenbin Chen; Bin Wang (Journal of Environmental Chemical Engineering, 2025)

Protein structural transitions and cryo-stability of shrimp gel: Effects of setting time at 30 °C in a novel processing system - Kaina Duan; Lechang Sun; Jie-ting Geng; Wenge Yang; Huamao Wei; Tao Huang; Ru Jia (Innovative Food Science & Emerging Technologies, 2025)

G1-mediated OsMADS1 repression regulates sterile lemma development in rice - Xuemei Qin; Jinliang Sun; Ru Li; Weijian Cen; Rongbai Li; Jijing Luo (Plant Cell Reports, 2025)

Integration of human sensory evaluation, intelligent E-tongue/E-nose systems, microbiomics, and metabolomics to comprehensively analyze flavor characteristics and dietary improvement mechanisms of processed Buddha's hand fruit - Zi-Xuan Ding; Yue-Hua Chen; Jia-Nuo Zhang; Wen-Yu Wang; Xin-Ru Zhang; Rui-Bo Sun; Hui Zhang; Ming Xie; Hui-Peng Song (Food Bioscience, 2025)

Design of 2D/2D Pt SA-MoS2/ZnIn2S4 photocatalysts for boosting hydrogen production - Xue-Lu Chen; Miao Ni; Yan-Ru Li; Yi-An Pan; Chen Chi; Yi Yang; Si-Meng Li; Sudip Biswas; Yi-Bai Sun; Xing-Hua Xia (Chemical Engineering Journal, 2025)

Anaerobic Digestion Enhances the Comprehensive Utilization of Shaddock Peel: Methane Production, Biochar Preparation, and CO2 Capture - Chengcheng Cao; Ru Li; Huantao Dai; Yan Zhao; Ling Sun; Xinheng Zhuang; Xueyang Zhang (Water, Air, & Soil Pollution, 2025)

Microbial life-history strategies mediate temperature effects on organic carbon pools in black soils - Lihui Lyu; Chaoqun Wang; Kunkun Fan; Jiasui Li; Teng Yang; Guifeng Gao; Ru Sun; Jiao Wang; Xiyuan Xu; Yuxiao Zhang; Yuying Ma; Jiabao Zhang; et al. (Soil Ecology Letters, 2025)

Anti-disintegration property of red soil treated with building gypsum powder - Yinlei Sun; Zhen Li; Xuan-Chen Lin; Qing-Ru Du; Xi Zou; Xianwei Zhang (Applied Clay Science, 2025)

Architectural features and antioxidative biofunctionality of a novel pectin from Angelica keiskei Koidz - Si-Ru Chen; Yu-Ru Zhu; Li-Ting He; Hong-Liang Sun; Jing Huang; Yan-Zi Yang; Hua-Jun Zhao; Bo Yang; Meng-Xia Yan (Natural Product Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Improved antifouling and regeneration capability of polyaniline-modified halloysite nanotube/MXene composite membranes - Jing-Yi Feng; Wen-Hao Geng; Ru-Yu Chang; Yu-Han Wang; Yue-Xin Wang; Ze-Long Bao; Wen-Yi Sun; Lu-Yao Tian; Di Zhang; Hong-Zhang Geng (Journal of Water Process Engineering, 2025)

Combining machine learning to explore the influence of VOCs and meteorological factors on ozone concentration: A case study of a chemical park in Shenyang, China - Qi Jiang; Nan Wang; Zhenling Jin; Xuebin Sun; Jiayin Wang; Ru Li (Atmospheric Research, 2025)

Systematic review of natural coumarins in plants (2019–2024): Chemical structures and pharmacological activities - Ze-Dong Nan; Ying Shang; Yi-Dong Zhu; Hui Zhang; Ru-Ru Sun; Jing-Jing Tian; Zhi-Bo Jiang; Xiao-Li Ma; Changcai Bai (Phytochemistry, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Zirconium phosphate nanonetworks for enhanced soft tissue integration and antibacterial performance of zirconia implant abutments - Yingyue Sun; Qihong Zhang; Shuyi Wu; Kendrick Hii Ru Yie; Lei Cai; Yinyan Zhang; Wen Si; Huan Cheng; Zijian Zheng; Peng Gao; Jinsong Liu; Lei Lu (Chemical Engineering Journal, 2025)

Four saprobic species associated with Mahonia in Guizhou Province, China - Ya-Ru Sun; Kevin D. Hyde; Ning-Guo Liu; Fatimah O. Al-Otibi; Yong Wang; Ruvishika S. Jayawardena (Mycological Progress, 2025)

Floated Bi4Ti3O12@MoS2 p-n heterojunction anti-fouling hydrogels for efficient seawater purification - Ying Liu; Bingyan Ni; Ruotong Ru; Linlin Zhang; Hongfei Sun; Jianjun Liao; Cheng Li; Dexin Wang; Xiaodong Zhang; Wei Zhou (Journal of Environmental Chemical Engineering, 2025)

Efficient release and possible mechanism of polyphenols in the pomace of chokeberry (Aronia melanocarpa L.) through solid-state fermentation using Trichoderma viride - Yuhang Xiao; Xinyi Li; Huimin Zhang; Yiwei Zhu; Weiman Gao; Shijing Jiang; Guangjiao Ru; Aidong Sun (Food Bioscience, 2025)

Differential analysis of microorganisms and flavor substances during drying of scallops (Chlamys farreri) based on high-throughput sequencing and headspace gas chromatography-mass spectrometry (HS-GC-MS) - Jing-ru Chen; Jia-bo Huang; Shi-meng Sun; Peng-fei Jiang (Food Bioscience, 2025)

Recent duplications and rare structural variations revealed by comparative sequence analysis of low molecular weight glutenin subunits (LMW-GS) genes re-identified using LMWgsFinder in 26 genomes of the grass family - Shengli Zhang; Xiaojing Shan; Yun Wang; Tairui Lu; Daxing Xu; Han Gong; Yuchao Fan; Yuanyuan Guan; Junjie Zhao; Haili Sun; Dongfang Li; Haiyan Hu; et al. (Theoretical and Applied Genetics, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Lifetime probabilities of developing and dying from cancer in China: comparison with Japan and the United States in 2022 - Qian Zhu; Yifei Yao; Ru Chen; Bingfeng Han; Shaoming Wang; Li Li; Kexin Sun; Rongshou Zheng; Wenqiang Wei (Science China Life Sciences, 2025)

Metallization-mediated charge transfer in cocrystals for efficient photocatalytic decontamination of mustard-gas simulant - Li Zhang; Xiao-Lin Liu; Chen Sun; Yu-Ting Luo; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2025)

Design and optimization of average coolant temperature control system for the small lead–bismuth fast reactor - Ru Zhang; Aodi Sun; Muping Li; Peiwei Sun; Xinyu Wei (Annals of Nuclear Energy, 2025)

Characterizing temporal trends and meteorological influences on ozone pollution in Shenyang region (2018–2021) - Shuangshuang Wu; Le Hou; Xuebin Sun; Min Liu; Nan Wang; Ru Li (Air Quality, Atmosphere & Health, 2025)

Sediment Provenance and Facies Analysis of the Huagang Formation in the Y-Area of the Central Anticlinal Zone, Xihu Sag, East China Sea - Xiao Ma; Wei Yan; Yi Yang; Ru Sun; Yue Chao; Guoqing Zhang; Chao Yang; Shudi Zhang; Dapeng Su; Guangxue Zhang; Hong Xu (Journal of Marine Science and Engineering, 2025)
Recent breakthrough exploration wells in the Huagang Formation in the Y-area of the central anticlinal zone of the Xihu Sag have confirmed the significant exploration potential of structure–lithology complex hydrocarbon reservoirs. However, limited understanding of the provenance system, sedimentary facies, and microfacies has hindered further progress in complex hydrocarbon exploration. Analysis of high-precision stratigraphic sequences and seismic facies data, mudstone core color, grain-size probability cumulative curves, core facies, well logging facies, lithic type, the heavy-mineral ZTR index, and conglomerate combinations in drilling sands reveals characteristics of the source sink system and provenance direction. The Huagang Formation in the Y-area represents an overall continental fluvial delta sedimentary system that evolved from a braided river delta front deposit into a meandering river channel large-scale river deposit. The results indicate that the primary provenance of the Huagang Formation in the Y-area of the Xihu Sag is the long-axis provenance of the Hupi Reef bulge in the northeast, with supplementary input from the short-axis provenance of the western reef bulge. Geochemical analysis of wells F1, F3, and G in the study area suggests that the prevailing sedimentary environment during the period under investigation was characterized by anoxic conditions in nearshore shallow waters. This confirms previous research indicating strong tectonic reversal in the northeast and a small thickness of the central sand body unrelated to the flank slope provenance system. The aforementioned findings deviate from conventional understanding and will serve as a valuable point of reference for future breakthroughs in exploration.

Location optimization of unmanned aerial vehicle (UAV) drone port for coastal zone management: The case of Guangdong coastal zone in China - Jia Sun; Sijing Shu; Hongda Hu; Yingbin Deng; Zhao Li; Shengnan Zhou; Yue Liu; Minwen Dang; Wumeng Huang; Zhiwei Hou; Xiaoling Yin; Ru Zhang; et al. (Ocean & Coastal Management, 2025)

Pathways for supply security and carbon-neutral transition in the oil products industry: A comprehensive technology portfolio evaluation - Li Shang; Zheng Lyu; Nannan Sun; Guofei Shen; Qun Shen; Ru Guo; Wei Wei (Journal of Cleaner Production, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Origin and evolution of slope-confined canyons and their relationship with gas hydrate accumulation in the northwestern Qiongdongnan Basin, South China Sea - Zigui Chen; Tao Jiang; Wenzhao Sun; Yue Chen; Cong Cheng; Ru Yin (Geomorphology, 2025)

Advanced fabrication of three-dimensional bicontinuous MXene/agarose composite monoliths for high-selective rapid separation of antibodies - Xiang-Dong Xu; Jing Li; Jun-Qi Zhang; Yuan Peng; Chen-Mei Sun; Ru-Qi Liang; Jian-Bo Qu (Chemical Engineering Journal, 2025)

Astragalus polysaccharide/carboxymethyl chitosan/sodium alginate based electroconductive hydrogels for diabetic wound healing and muscle function assessment - Letian Tang; Shuyang Xie; Danyang Wang; Yiying Wei; Xiaopu Ji; Yicheng Wang; Nana Zhao; Zonglei Mou; Baoping Li; Wan Ru Sun; Ping Yu Wang; Nicola Paccione Basmadji; et al. (Carbohydrate Polymers, 2025)

Automatic and integrated detection of nucleic acid by using a dual-mode thermal controlled digital microfluidic chip - Jiaqi Liao; Chonghao Li; Jiajia Liu; Hao Cheng; Linmin Li; Guixi Tang; Ru Huang; Yating Lu; Siyue Chen; Qian Zhang; Hao Chen; Qinyuan Chen; et al. (Analytica Chimica Acta, 2025)

Isoalcanivorax beigongshangi sp. nov., isolated from the fermented grains of Chinese baijiu - Tong-Xi Zhang; Yi-Ming Li; Hao-Yue Gu; Ru Zhang; Zhan-Bin Sun; Han-Xu Pan; Qing Ren (Antonie van Leeuwenhoek, 2025)

Association of anthropogenic heat with asthma and related symptoms among children in China: A novel index reflecting climate change - Feng-Wen Shan; Xuan Liu; Ming-Kun Sun; Zhengmin Qian; Michael G. Vaughn; Niraj R. Chavan; Shu-Li Xu; He-Hai Huang; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Li-Zi Lin; et al. (Sustainable Cities and Society, 2024)

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Recent advances in methane and hydrogen production from lignocellulosic degradation with anaerobic fungi - Jinsong Liang; Shiqi Liu; Zhangping Du; Ru Zhang; Longyi Lv; Li Sun; Mohammad Nabi; Guangming Zhang; Panyue Zhang (Bioresource Technology, 2024)

Cell-permeable PI3 kinase competitive peptide inhibits KIT mutant mediated tumorigenesis of gastrointestinal stromal tumor (GIST) - Zongying Jiang; Yue Guo; Jun Shi; Shaoting Zhang; Liangying Zhang; Yapeng Wang; Guofu Li; Ru Bai; Hui Zhao; Jianmin Sun (Molecular Biology Reports, 2024)

A ratiometric fluorescent probe based on UiO-66-TCPP for selective and visual detection of quercetin in food - Yiran Wang; Xiaolong Sun; Yufeng Zhou; Jiachen Liu; Huayue Zhu; Ru Jiang; Yingjie Miao; Yongqian Fu (Food Chemistry, 2024)

Nickel sulfide nanorods encapsulated in Nitrogen-Doped carbon on nickel foam in situ derived from Saccharomycetes cerevisiae for the selective oxidation of biomass - Hao Chen; Si-Ru Chen; Qing Yang; Le-Xing You; Qun-Feng Ye; Ai-Jun Wang; Dong-Hai Lin; Yan-Xia Jiang; Shi-Gang Sun (Chemical Engineering Journal, 2024)

Heterogeneous degradation kinetics of typical pyrimidine pesticides toward OH radicals - Ru Chen; Dandan Chen; Qiang Niu; Lu Fan; Mingchao Sun; Zhengzheng Yang; Changgeng Liu (Atmospheric Environment, 2024)

Fruit flexible collecting trajectory planning based on manual skill imitation for grape harvesting robot - Jiahui Sun; Qingchun Feng; Yifan Zhang; Mengfei Ru; Yajun Li; Tao Li; Chunjiang Zhao (Computers and Electronics in Agriculture, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

A bifunctional thiobenzamide additive for improvement of cathode kinetics and anode stability in lithium-sulfur batteries - Junpeng Rao; Tong Yu; Youshuang Zhou; Ru Xiao; Yaozu Wang; Zhuoyan Qu; Dean Shi; Zhenhua Sun; Feng Li (Chemical Engineering Journal, 2024)

Understanding the evolution of molybdenum-nitrogen doped carbon with long-term durability for efficient oxygen reduction reaction - Xingyu Luo; Bingbao Mei; Ru Feng; Xiaofeng Xu; Zhongyan Zhang; Mingyu Ou; Fanfei Sun; Huajun Zheng; Meiqin Shi (Chemical Engineering Journal, 2024)

Enhancing osseointegration and angiogenesis of Titanium implants through KMnO4-Modified Montmorillonite nano-clay coating - Lifeng Xiong; Binwei Dai; Baodi Yin; Kendrick Hii Ru Yie; Haobo Sun; Yang Liu; Zheyuan Liu; Ahmed S. Mahany; Huan Cheng; Lihua Xu; Peng Gao; Lei Lu; et al. (Chemical Engineering Journal, 2024)

Lowering Schottky barrier in MoC-based cocatalyst via heteroatoms tunning for enhanced photocatalytic hydrogen evolution - Ru-zhou Miao; Yu-long Bao; Guang Yang; Ying-jie Sun; Xiao-jing Wang; Jun Zhao; Hui-ying Mu; Fa-tang Li (Chemical Engineering Journal, 2024)

Improved prediction of swimming talent through random forest analysis of anthropometric and physiological phenotypes - Cheng Liu; Bingxiang Xu; Kang Wan; Qin Sun; Ruwen Wang; Yue Feng; Hui Shao; Tiemin Liu; Ru Wang (Phenomics, 2024)

Genesis of Pb–Zn-Ag-Sb mineralization in the Tethys Himalaya, China: Early magmatic-hydrothermal Pb–Zn(-Ag) mineralization overprinted by Sb-rich fluids - Xiang Sun; Ru-Yue Li; Hao-Yu Sun; Paul H. Olin; M. Santosh; Bin Fu; Jun Deng (Mineralium Deposita, 2024)

Sodium Selenite Ameliorates Silver Nanoparticles Induced Vascular Endothelial Cytotoxic Injury by Antioxidative Properties and Suppressing Inflammation Through Activating the Nrf2 Signaling Pathway - Yunyun Ma; Lei Wang; Jing He; Xueping Ma; Jingjing Wang; Ru Yan; Wanrui Ma; Huiyan Ma; Yajuan Liu; Hongqian Sun; Xiaoxia Zhang; Shaobin Jia; et al. (Biological Trace Element Research, 2024)
Silver nanoparticles (AgNP) are the dominant nanomaterials in commercial products and the medical field, but the widespread occurrence of AgNP has become a global threat to human health. Growing studies indicate that AgNP exposure can induce vascular endothelial toxicity by excessive oxidative stress and inflammation, which is closely related to cardiovascular disease (CVD), but the potential intrinsic mechanism remains poorly elucidated. Thus, it has been crucial to control the toxicological effects of AgNP in order to improve their safety and increase the outcome of their applications. Multiple researches have demonstrated that sodium selenite (Se) possesses the capability to counteract the toxicity of AgNP, but the functional role of Se in AgNP-induced CVD is largely unexplored. The aim of this study was to explore the potential protective effect of Se on AgNP-induced vascular endothelial lesion and elucidate the underlying mechanisms. An in vivo model of toxicity in animals was established by the instillation of 200 µL of AgNP into the trachea of rats both with (0.2 mg/kg/day) and without Se treated. In vitro experiments, human umbilical vein endothelial cells (HUVECs) were incubated with AgNP (0.3 µg/mL ) and Se for a duration of 24 h. Utilizing transmission electron microscopy, we observed that the internalization of AgNP-induced endothelial cells was desquamated from the internal elastic lamina, the endoplasmic reticulum was dilated, and the medullary vesicle formed. Se treatment reduced the levels of vascular cell adhesion molecule-1 (VCAM-1) and intercellular adhesion molecule-1 (ICAM-1), inhibited the release of pro-inflammatory cytokines (specifically tumor necrosis factor (TNF)-α, interleukin (IL)-1β and IL-6), improved endothelial cell permeability, integrity, and dysfunction, and prevented damage to the aortic endothelium caused by AgNP. Importantly, we found that Se showed the capacity against AgNP with biological functions in guiding the intracellular reactive oxygen species (ROS) scavenging and meanwhile exhibiting anti-inflammation effects. Se supplementation decreased the intracellular ROS release and suppressed NOD-like receptor protein 3 (NLRP3) and nuclear factor kappa-B (NF-κB) mediated inflammation within AgNP-intoxicated rats and HUVECs. The anti-oxidant stress and anti-inflammatory effects of Se were at least partly dependent on nuclear factor erythroid 2-related factor 2 (Nrf2). Overall, our results indicated that the protectiveness of Se against AgNP-induced vascular endothelial toxicity injury was at least attributed to the inhibition of oxidative ROS and pro-inflammatory NF-κB/NLRP3 inflammasome by activating the Nrf2 and antioxidant enzyme (HO-1) signal pathway.

Deposition and termination of Neoproterozoic iron formations (NIFs): New insights from NIFs in China - Hui Ye; Chang-Zhi Wu; Weiqiang Li; Ru-Xiong Lei; Xiaohui Sun; Weiduo Hao; Kurt O. Konhauser (Earth-Science Reviews, 2024)

Effect of guar gum, gelatin, and pectin on moisture changes in freeze-dried restructured strawberry blocks - Jiaqi Hu; Xiyun Sun; Hongwei Xiao; Chunju Liu; Feifei Yang; Wuyi Liu; Yulong Wu; Yaoyao Wang; Ru Zhao; Haiou Wang (Food Chemistry, 2024)

Enhancing open-circuit voltage and suppression of energy loss in ternary organic photovoltaics utilizing carbazole/bicarbazole-based guest donors - Chun-Yu Lin; Bing-Huang Jiang; Pei-Jui Weng; Yu Hsuan Lin; Yu-Wei Su; Hui-Shan Shih; Zhong-En Shi; Yan-Ru Lin; Jijitha Vailassery; Shih-Sheng Sun; Chih-Ping Chen; Yuan Jay Chang (Chemical Engineering Journal, 2024)

Molecular insights into the interactions of theaflavin and epicatechin with different lipid bilayer membranes by molecular dynamics simulation - Rong-zu Nie; Huo-min Luo; Jing-yu Chen; Li-heng Sun; Zi-bo Wang; Zhen-ping Zhang; Ya-ru Bao (Chemistry and Physics of Lipids, 2024)

Rapid, sensitive, and visual detection of pseudorabies virus with an RPA-CRISPR/EsCas13d-based dual-readout portable platform - Dong You; Tong Xu; Bing-Zhou Huang; Fang Wu; Li-Shuang Deng; Zhe-Yan Liu; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; Yuan-Cheng Zhou; Si-Yuan Lai; et al. (Analytica Chimica Acta, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Effects of different phosphorylation times and pH on fish gelatin: Functional properties, structural and mechanism analysis - Bin Hu; Shijie Cen; Wanyi Sun; Shengnan Zhan; Ru Jia; Changrong Ou; Tao Huang (Food Hydrocolloids, 2024)

Adsorption Kinetics and Stabilization Effects of Various Forms of Phosphorus on Schwertmannite - Shuqin Bai; Ru Ya; Shuxuan Chen; Niqi Ao; Yiwen Wu; Qiyao Sun; Han Yang; Shuangfeng Zhao (Water, Air, & Soil Pollution, 2024)

Colonization ability and uniformity of resources and environmental factors determine biological homogenization of soil protists in human land‐use systems - Zhi‐Peng Li; Hua‐Yuan Shangguan; Haifeng Yao; Xiao‐Ru Yang; Yuri Mazei; Biao Zhu; Stefan Scheu; Xin Sun (Global Change Biology, 2024)
Humans have substantially transformed the global land surface, resulting in the decline in variation in biotic communities across scales, a phenomenon known as “biological homogenization.” However, different biota are affected by biological homogenization to varying degrees, but this variation and the underlying mechanisms remain little studied, particularly in soil systems. To address this topic, we used metabarcoding to investigate the biogeography of soil protists and their prey/hosts (prokaryotes, fungi, and meso‐ and macrofauna) in three human land‐use ecosystem types (farmlands, residential areas, and parks) and natural forest ecosystems across subtropical and temperate regions in China. Our results showed that the degree of community homogenization largely differed between taxa and functional groups of soil protists, and was strongly and positively linked to their colonization ability of human land‐use systems. Removal analysis showed that the introduction of widespread, generalist taxa (OTUs, operational taxonomic units) rather than the loss of narrow‐ranged, specialist OTUs was the major cause of biological homogenization. This increase in generalist OTUs seemingly alleviated the negative impact of land use on specialist taxa, but carried the risk of losing functional diversity. Finally, homogenization of prey/host biota and environmental conditions were also important drivers of biological homogenization in human land‐use systems, with their importance being more pronounced in phagotrophic than parasitic and phototrophic protists. Overall, our study showed that the variation in biological homogenization strongly depends on the colonization ability of taxa in human land‐use systems, but is also affected by the homogenization of resources and environmental conditions. Importantly, biological homogenization is not the major cause of the decline in the diversity of soil protists, and conservation and study efforts should target at taxa highly sensitive to local extinction, such as parasites.

The first record of the Gondwanan seed fern Dicroidium Gothan in Laurasia - Yanqi Sun; Shenghui Deng; Yuanzheng Lu; Ru Fan; Xueying Ma; Dan Lyu (Review of Palaeobotany and Palynology, 2024)

Dual-role KCl-assisted fabrication of porous carbon with controllable architecture from coal liquefaction residue for supercapacitors - Xiaoxia Yang; Guoxiao Sun; Fei Wang; Long Chen; Zhuangzhuang Zhang; Yanzhong Zhen; Danjun Wang; Feng Fu; Ru’an Chi (Fuel, 2024)

Enteral nutrition in the management of acute pancreatitis: Modulates gut microbiome and alleviates inflammation - Fang-Yuan Yang; Yi-Jing Cai; Xiao-Ying Niu; Shun-Fu Wang; Yu-Qi Wang; Sabola Eluby Esmie; Rui-Cong Chen; Sheng-Jie Dai; Hong-Ru Kong; Hong-Wei Sun; Ke-Qing Shi (Food Bioscience, 2024)

Biomimetic design of micro- and nano-wrinkle wood surface via coating reinforced with hyperbranched polymer grafted cellulose nanofibers for skin-tactile performance - Ru Liu; Yuhui Sun; Yingchun Sun; Hui Li; Minggui Chen; Ling Long; Jingya Gong; Bin Lv; Yonghao Ni (Carbohydrate Polymers, 2024)

Panax quinquefolius saponins and panax notoginseng saponins attenuate myocardial hypoxia-reoxygenation injury by reducing excessive mitophagy - Junyan Xia; Cong Chen; Yanan Sun; Sinai Li; Yuxuan Li; Bai-Ru Cheng; Yanting Pang; Yan Li; Dong Li; Qian Lin (Cell Biochemistry and Biophysics, 2024)

Glycosylation with different saccharides on the gelling, rheological and structural properties of fish gelatin - Hulin Geng; Wanyi Sun; Shengnan Zhan; Ru Jia; Qiaoming Lou; Tao Huang (Food Hydrocolloids, 2024)

Comparative evaluation of acid-resistant nanofiltration membranes for heavy metal removal in acidic wastewater - Chun Cui; Cong Luo; Tian Tian; Ru Feng; An-Kang Li; Shi-Peng Sun; Xue-Li Cao (Desalination, 2024)

Exogenous additive ferric sulfate regulates sulfur-oxidizing bacteria in cow manure composting to promote carbon fixation - Ru Sun; Qunliang Li (Environmental Science and Pollution Research, 2024)

Nitrogen addition does not alter symmetric responses of soil respiration to changing precipitation in a semi-arid grassland - Lingjie Kong; Jian Song; Jingyi Ru; Jiayin Feng; Jiawei Hou; Xueke Wang; Qingshan Zhang; Haidao Wang; Xiaojing Yue; Zhenxing Zhou; Dasheng Sun; Jiajia Zhang; et al. (Science of The Total Environment, 2024)

Sulfur and nitrogen co-metabolism during composting: A role of sodium sulfide in regulating microbial communities and functional genes - Shuaipeng Liu; Heng Lu; Ao Wang; Xiaojing Chen; Hongmei Yang; Xueling Liang; Ru Sun; Xiaoli Wen; Qunliang Li (Journal of Environmental Chemical Engineering, 2024)

Protective effect of cilostazol on vascular injury in rats with acute ischemic stroke complicated with chronic renal failure - Ru Sun; Qun Gu; Xufeng Zhang; Ruiqi Zeng; Dan Chen; Jingjing Yao; Jingjing Min (Toxicological Research, 2024)
Chronic renal failure (CRF) resulting in vascular calcification, which does damage to blood vessels and endothelium, is an independent risk factor for stroke. It has been reported that cilostazol has a protective effect on the focal cerebral ischemic infarct. However, its impact on vascular injury in CRF combined stroke and its molecular protection mechanism have not been investigated. In this study, we carried out the effect of cilostazol on CRF combined stroke rats, and the results confirmed that it improved the neurobehavior, renal function as well as pathologic changes in both the kidney and brain. In addition, the inflammation and oxidative stress factors in the kidney and brain were suppressed. Moreover, the rates of brain edema and infarction were decreased. The injured brain-blood barrier (BBB) was recovered with less Evans blue extravasation and more expressions of zonula occludens-1(ZO-1) and occludin. More cerebral blood flow (CBF) in the ipsilateral hemisphere and more expression of CD31 and vascular endothelial growth factor (VEGF) in brain and kidney were found in the cilostazol group. Furthermore, cell apoptosis and cell autophagy became less, on the contrary, proteins of vascular endothelial growth factor receptor 2 (VEGFR2) after the cilostazol treatment were increased. More importantly, this protective effect is related to the pathway of Janus Kinase (JAK)/signal transducer and activator of transcription 3 (STAT3), mammalian target of rapamycin (mTOR), and the hypoxia inducible factor-1α (HIF-1α). In conclusion, our results confirmed that cilostazol exerted a protective effect on the brain and kidney function, specifically in vascular injury, oxidative stress, cell apoptosis, cell autophagy, and inflammation response in CRF combined with stroke rats which were related to the upregulation of JAK/STAT3/mTOR signal pathway.

Conductive nanofiltration membranes via in situ PEDOT-polymerization for electro-assisted membrane fouling mitigation - Tian-Zhi Jia; Ru Feng; Chun Cui; Qian Chen; Levente Cseri; Rong-Fei Zhou; Gyorgy Szekely; Xue-Li Cao; Shi-Peng Sun (Water Research, 2024)

Communication mediated interaction between bacteria and microalgae advances photogranulation - Xiaogang Wu; Lingrui Kong; Yiming Feng; Ru Zheng; Jianhang Zhou; Jingqi Sun; Sitong Liu (Science of The Total Environment, 2024)

Facile synthesis of hydroxylated triazine-based magnetic microporous organic network for ultrahigh adsorption of phenylurea herbicides: An experimental and density-functional theory study - Lu Liu; Lu-Qin Qiao; Feng Liu; Qian-Yun Sun; Yan-Fang Zhao; Xiao-Li Wang; Na Li; Hai-Long Jiang; Xiang-Feng Chen; Ming-Lin Wang; Yong-Ning Wu; Ru-Song Zhao (Journal of Hazardous Materials, 2024)

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Preparation and characterization of pea protein isolate-egg white protein composite gels - Yu-Ru Zhao; Ning Peng; Chenying Wang; Ying-Qiu Li; Yan Liang; Zhi-Wei Guo; Ao-Yue Sun; Xidong Ren (Food Hydrocolloids, 2024)

Optimizing maize productivity: A sustainable approach integrating straw derivatives and film mulching in rainfed agriculture - Rui Qian; Zijun Ma; Yunyun Yang; Ru Guo; Fei Han; Jinjin Wang; Xiaoling Wang; Baoping Sun; Xiaolong Ren; Xiaoli Chen; Zhikuan Jia (Field Crops Research, 2024)

Experimental and theoretical study on seismic behavior of a new UHPFRC sandwich wall and wall-wall joint - Ru-Rui Liu; Ran Ding; Yong-Tao Sun; Jian-Sheng Fan; Ding-Qiu Chen; Jian-Chao Xu (Engineering Structures, 2024)

Can straw recycling achieve sustainable agriculture at the smallholder level? A case in a semi-arid region - Rui Qian; Ru Guo; Qingxuan Yang; Muhammad Asad Naseer; Baoping Sun; Longlong Wang; Jian Zhang; Xiaolong Ren; Xiaoli Chen; Zhikuan Jia (Journal of Cleaner Production, 2024)

Low-temperature fabrication of potassium single-atom solid base catalysts with high activity in transesterification - Xiang-Bin Shao; Xing-Ru Song; Song-Song Peng; Xiao-Qin Zheng; Shi-Chao Qi; Peng Tan; Xiao-Qin Liu; Lin-Bing Sun (Chemical Engineering Journal, 2024)

Bifidobacteria in disease: from head to toe - Weiliang Zhang; Qiang Jia; Mingming Han; Xin Zhang; Limin Guo; Shichao Sun; Wenhui Yin; Cunxiang Bo; Ru Han; Linlin Sai (Folia Microbiologica, 2024)

Peduncle collision-free grasping based on deep reinforcement learning for tomato harvesting robot - Yajun Li; Qingchun Feng; Yifan Zhang; Chuanlang Peng; Yuhang Ma; Cheng Liu; Mengfei Ru; Jiahui Sun; Chunjiang Zhao (Computers and Electronics in Agriculture, 2024)

Accelerated removal of naproxen in the iron-based peracetic acid activation system by chloride ions: Enhancement of reactive oxidative species via the formation of iron-chloride complexes - Si-Ying Yu; Yang Shi; Chuan-Shu He; Yu-Dan Dong; Si Sun; Ru-Yan Ning; Zhao-Kun Xiong; Peng Zhou; Heng Zhang; Bo Lai (Journal of Hazardous Materials, 2024)

Expression of polyphenol oxidase of Litopenaeus vannamei and its characterization - Qian Hong; Yu-Lei Chen; Duanquan Lin; Ru-Qing Yang; Kai-Yuan Cao; Ling-Jing Zhang; Yi-Ming Liu; Le-Chang Sun; Min-Jie Cao (Food Chemistry, 2024)

Comammox plays a functionally important role in the nitrification of rice paddy soil with different nitrogen fertilization levels - Kai Zhang; Hui-Feng Sun; You-Cai Kang; Ran Jiang; Yan-Ren Wang; Ru-Yi Zhang; Sheng-Nan Zhang; Yang-Yang Li; Peng Li; Fan Yang; Sheng Zhou; Zhe-Xue Quan (Applied Soil Ecology, 2024)

Corrigendum to “Silica nanoparticles promote oxLDL-induced macrophage lipid accumulation and apoptosis via endoplasmic reticulum stress signaling” [Sci. Total Environ., 631-632 (2018): 570-579] - Caixia Guo; Ru Ma; Xiaoying Liu; Tian Chen; Yang Li; Yang Yu; Junchao Duan; Xianqing Zhou; Yanbo Li; Zhiwei Sun (Science of The Total Environment, 2023)

Paleoproterozoic crustal evolution of the Tarim Craton, NW China: Constraints from geochronology and geochemistry of orthogneisses and granitic veins in the Xingdi region of the Quruqtagh Block - Xiao-Hui Sun; Xiang Li; Ru-Xiong Lei; Matthew J. Brzozowski; Hua-Dong Ma; Wei Li; Li-Ming Xiong; Ming-Yi Xia; Chang-Zhi Wu (Precambrian Research, 2023)

Magmatic–hydrothermal evolution of the Koktokay No. 3 pegmatite, Altai, northwestern China: Constraints from in situ boron isotope and chemical compositions of tourmaline - Rong Yin; Xiao-Long Huang; Ru-Cheng Wang; Gang-Jian Wei; Yi-Gang Xu; Yu Wang; Xiao-Ming Sun; Le Zhang; Xiao-Ping Xia (Lithos, 2023)

Antioxidant CeO2 doped with carbon dots enhance ammonia production by an electroactive Azospirillum humicireducens SgZ-5T - Gao-Kai Wu; Meng-Xin Zhao; Si-Ru Chen; Yi-Nan Sun; Su-Fang Qin; Ai-Jun Wang; Qun-Feng Ye; Hend Alwathnani; Le-Xing You; Christopher Rensing (Chemosphere, 2023)

Global, regional, and national lifetime probabilities of developing cancer in 2020 - Rongshou Zheng; Shaoming Wang; Siwei Zhang; Hongmei Zeng; Ru Chen; Kexin Sun; Li Li; Freddie Bray; Wenqiang Wei (Science Bulletin, 2023)

USP22 knockdown protects against cerebral ischemia/reperfusion injury via destabilizing PTEN protein and activating the mTOR/TFEB pathway - Yanling Li; Jing Gao; Chuntian Liu; Ning Bu; Shuqin Zhan; Haiqin Wu; Ru Zhang; Hong Sun; Hong Fan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Inter-brain neural mechanism and influencing factors underlying different cooperative behaviors: a hyperscanning study - Qingming Liu; Huimin Cui; Bincan Huang; Yingying Huang; Huimeng Sun; Xinyi Ru; Mingming Zhang; Wei Chen (Brain Structure and Function, 2023)

YOLACTFusion: An instance segmentation method for RGB-NIR multimodal image fusion based on an attention mechanism - Cheng Liu; Qingchun Feng; Yuhuan Sun; Yajun Li; Mengfei Ru; Lijia Xu (Computers and Electronics in Agriculture, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

Unveiling the hidden role of aquatic viruses in hydrocarbon pollution bioremediation - Jinlong Ru; Jinling Xue; Jianfeng Sun; Linda Cova; Li Deng (Journal of Hazardous Materials, 2023)

Ozone exposure associates with sperm quality indicators: Sperm telomere length as a potential mediating factor - Zhong-Hua Lu; Bin Sun; Yi-Xin Wang; Ya-Ru Wu; Yu-Jie Chen; Sheng-Zhi Sun; Shi-Jia Liang; Song Xu; Hao Chang; Heng-Gui Chen; Jie Zhang (Journal of Hazardous Materials, 2023)

Ferritinophagy activation and sideroflexin1-dependent mitochondrial iron overload contribute to patulin-induced cardiac inflammation and fibrosis - Wen-Chang Sun; Ning-Ning Wang; Ru Li; Xian-Ce Sun; Jia-Wei Liao; Guang Yang; Shuang Liu (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Metabolomic profiling of Panax ginseng in response to Fusarium solani infection - Guijia Zhao; Shuyang Xing; Yang Wang; Xu Yang; Ru Sun; Lin Feng; Jifeng Wang; Tianxia Sun; Wenhui Lian; Yu Zhao (Physiological and Molecular Plant Pathology, 2023)

Iron reduction in composting environment synergized with quinone redox cycling drives humification and free radical production from humic substances - Ru Sun; Mengxin Fu; Liangcai Ma; Yucheng Zhou; Qunliang Li (Bioresource Technology, 2023)

A Co2N/CoP p-n junction with modulated interfacial charge and rich nitrogen vacancy for High-Efficiency water splitting - Chunfang Guo; Hui Xue; Jing Sun; Niankun Guo; Tianshan Song; Jiawen Sun; Yi-Ru Hao; Qin Wang (Chemical Engineering Journal, 2023)

Classification and applicable conditions of water rights systems - Yuanyuan Sun; Shaofeng Jia; Ru Jia (Water Resources Management, 2023)

Thymic tuft cells: potential “regulators” of non-mucosal tissue development and immune response - Jun Sun; Ming-xin Li; Yi-meng Xie; Ya-ru Zhang; Yu-rong Chai (Immunologic Research, 2023)

Soil extracellular enzymes characteristics and their controlling factors along the elevation gradient in Qinghai-Tibet Plateau, China - Yan-xia Pan; Xin-rong Li; Zeng-ru Wang; Li Feng; Lei Huang; Bing-yao Wang; Jing-yao Sun (Applied Soil Ecology, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Silica nanoparticles promoted pro-inflammatory macrophage and foam cell transformation via ROS/PPARγ/NF-κB signaling - Caixia Guo; Xinying Zhao; Ru Ma; Lingnan Zhu; Yueyue Chen; Zhu Yang; Zongwei Cai; Zhiwei Sun; Yanbo Li (Science of The Total Environment, 2023)

Maleic anhydride promotes humus formation via inducing functional enzymes response in composting - Mengxin Fu; Ziyi Cao; Ru Sun; Xiaoli Wen; Yiwu Wang; Kecheng Li; Qunliang Li (Bioresource Technology, 2023)

Projections from the Prefrontal Cortex to Zona Incerta Mediate Fear Generalization - Kun Tong; Guang-Kai Bu; Si-Qi Jing; Tong Wu; Yu-Tong Song; Yue You; Le Liu; Yuan-Hao Chen; Jing-Ru Hao; Nan Sun; Can Gao (Neuroscience Bulletin, 2023)

Ganglioside-focused Glycan Array Reveals Abnormal Anti-GD1b Auto-antibody in Plasma of Preclinical Huntington’s Disease - Tien-Wei Lin; Jung-Kai Chang; Yih-Ru Wu; Tsung-Hsien Sun; Yang-Yu Cheng; Chien-Tai Ren; Mei-Hung Pan; Jin-Lin Wu; Kuo-Hsuan Chang; Hwai-I Yang; Chiung-Mei Chen; Chung-Yi Wu; et al. (Molecular Neurobiology, 2023)

Research on fuzzy weighted gain scheduling water level control system of U-tube steam generator - Leilei Qiu; Yan Huo; Ru Zhang; Haomin Wang; Guanfu Jiang; Peiwei Sun; Xinyu Wei (Annals of Nuclear Energy, 2023)

Global trends in surface eddy mixing from satellite altimetry - Guangchuang Zhang; Ru Chen; Laifang Li; Hao Wei; Shantong Sun (Frontiers in Marine Science, 2023)
Mixing induced by oceanic mesoscale eddies can affect tracer distributions in the ocean and thus modulate the evolution of the physical and biochemical marine system. In the context of global warming, regionally different trends in eddy mixing could exist. Motivated by this hypothesis, we quantified the trend in surface eddy diffusivity, a metric widely used to quantify the eddy mixing rate, in the global ocean using satellite altimetry data. The global average of the particle-based eddy diffusivity increases by 284.1 m 2 s − 1 per decade during the period of 1994-2017, or 3.7% per decade relative to its climatological mean value. In 54% of the global ocean, eddy diffusivity shows an increasing trend. The diffusivity trend can be decomposed into two components: one related to changes in eddy mixing length and the other related to eddy velocity magnitude. In 73% of the global ocean, changes in eddy mixing length account for more than 50% of the diffusivity trend. The suppressed mixing length theory (SMLT) is employed to interpret the trend in eddy mixing length. SMLT well captures the sign of the trend in two of the representative regions. Among all the parameters (e.g., eddy size, phase speed) inherent in SMLT, the eddy velocity magnitude plays a dominant role in determining the trend in the SMLT-based eddy mixing length. Diagnosing the geostrophic eddy kinetic energy budget reveals that the dominant mechanism for the trend in eddy velocity magnitude is the pressure work induced by ageostrophic flows. Our results suggest that a time-dependent eddy parameterization scheme should be employed in non-eddy-resolving models to account for the trend in eddy mixing.

Cancer statistics in Chinese older people, 2022: current burden, time trends, and comparisons with the US, Japan, and the Republic of Korea - Wen Ju; Rongshou Zheng; Siwei Zhang; Hongmei Zeng; Kexin Sun; Shaoming Wang; Ru Chen; Li Li; Wenqiang Wei; Jie He (Science China Life Sciences, 2023)

Methylated Chromenoquinoline as a Novel Nucleus Fluorescent Probe for Nucleic Acid Imaging - Zhi-Hao Zhang; Qing Yu; Gang Zhang; Hai-Yan Peng; Ru Sun; Yu-Jie Xu; Jian-Feng Ge (Journal of Fluorescence, 2023)

Characteristics and driving factors of abandoned cultivated land in the hilly regions of southern China: A case study in Longnan, Jiangxi Province - Ze-bin Chen; Yong-lin Chen; Chao-jun Li; Jian-ping Lin; Pei-ru Chen; Wei-wei Sun; Zhi-wei Wan (Journal of Mountain Science, 2023)

Multidimensional identification of single and regional meteorological drought considering flash‐season synthesis employed daily standardized effective precipitation and drought index in Guangxi, China - Yang Yun‐chuan; Yang Jia‐zhen; Tian Yi; Liao Li‐ping; Gan Ru‐min; Wang Wei‐quan; Wang Ting‐yan; Mo Chong‐xun; Li Xun‐gui; Sun Gui‐kai (International Journal of Climatology, 2023)
The frequent occurrence of extreme drought events in Guangxi has caused huge losses to human beings and economy in the region for many years. Therefore, this study adopted run theory and the objective identification method of regional extreme events (OITREE) and then carried out the comprehensive feature identification of multidimensional elements such as intensity, duration and area of meteorological drought events based on the daily standardized effective precipitation and drought index (SWAP) sequence of Guangxi from 1979 to 2018a. By comparing the evolutionary characteristics of drought elements identified by grid SWAP statistical analysis and OITREE, an integrated optimization scheme combining the accuracy of grid analysis and area identification is formed in this study. It was confirmed that the above two analysis methods had good correlation and consistency in revealing the evolution process of multidimensional elements of drought events. In terms of the frequency of drought events over a long period of time and the comprehensive characteristics of each element, the identification results of the OITREE method can better reveal the comprehensive characteristics of drought in Guangxi. Furthermore, the study found that flash droughts and seasonal droughts occurred alternately and were superimposed concurrently in Guangxi, and there were significant differences in the multidimensional spatial and temporal characteristics of these two types of droughts. Specifically, the frequency of flash drought was 1.60–4.00 times·(a) −1 , the duration varied from 20 to 60 days·(a) −1 and the concentration point of drought had a region‐wide dispersion; while the frequency of seasonal drought was 0.82–1.65 times·(a) −1 , the duration varied from 40–105 days·(a) −1 and the concentration point of drought had a local concentration. The research results can provide effective scientific support for operational drought refined forecast and early warning, and smart regulation of drought disaster risk.

mRNA 3ʹ -UTR-mediate translational control through PAS and CPE in sheep oocyte - Chun-Ru Song; Ru-Jing Zhang; Fang-Rui Xue; Xiao-Jie Zhang; Xing-Yue Wang; Dui Sun; Kang Ding; Qi Yang; Xin-Yu Wang; Cheng-Guang Liang (Theriogenology, 2023)

Glycation of whey protein isolate and stachyose modulates their in vitro digestibility: Promising prebiotics as functional ingredients - Guang-yao Zhang; Cong Sun; Jing-ru Song; Wei-yi Jin; Yue Tang; Da-yong Zhou; Liang Song (Food Bioscience, 2023)

A Cre knockin mouse reveals specific expression of Agouti gene in mesenchymal lineage cells in multiple organs and provides a unique tool for conditional gene targeting - Xing-Ru Shen; He-Li Zhang; Xu-Bo Zhao; Yang-Ge Wang; Xiao-Yang Tan; Lipeng Gao; Ruilin Sun; Xin-Hua Liao (Transgenic Research, 2023)

An in-situ strategy to construct uracil-conjugated covalent organic frameworks with tunable fluorescence/recognition characteristics for sensitive and selective Mercury(II) detection - Xi-Rui Deng; A-Wei Hu; Sheng-Qian Hu; Wen-Li Yang; Chen Sun; Sai-Jin Xiao; Gui-Ping Yang; Qiong-Qing Zheng; Ru-Ping Liang; Li Zhang; Jian-Ding Qiu (Analytica Chimica Acta, 2023)

Extraction of weak hydrophobic sulforaphane from broccoli by salting-out assisted hydrophobic deep eutectic solvent extraction - Wen-wen Deng; Xue-ping Mei; Zi-jun Cheng; Tian-xiang gan; Xuan Tian; Jiang-nan Hu; Chuan-ru Zang; Bo Sun; Jing Wu; Yin Deng; Reza. A. Ghiladi; George H. Lorimer; et al. (Food Chemistry, 2023)

Dynamic changes in cell wall-degrading enzymes and physio-biochemistry of ginseng in response to fusarium oxysporum infection - Lin Feng; Guijia Zhao; Ru Sun; Jifeng Wang; Tianxia Sun; Shuyang Xing; Wenhui Lian; Yu Zhao (European Journal of Plant Pathology, 2023)

Molecular characterization of humic-like substances (HULIS) in atmospheric particles (PM2.5) in offshore Eastern China Sea (OECS) using solid-phase extraction coupled with ESI FT-ICR MS - Hao Sun; Zilan Wu; Xinyuan Kang; Chao Zhu; Limin Yu; Ru Li; Zhongsheng Lin; Jianmin Chen (Atmospheric Environment, 2023)

Combined effect of Cu- and ZnO- NPs on antibiotic resistance genes in an estuarine water - Yu-ru Chen; Rong-rong Sha; Xiao-li Sun; Xing-pan Guo; Yi Yang (Frontiers in Marine Science, 2023)
Most studies of whether and how nanoparticles (NPs) affect antibiotic resistance genes (ARGs) focus on testing single NPs type. In this study, we determined the combined effect of Cu- and ZnO- NPs in the water samples collected from the Yangtze River Estuary and found the effect differs greatly from that produced by individual NPs. The results showed that the Cu- and ZnO- NPs co-exposure resulted in an enrichment of ARGs, whereas individual Cu- and ZnO- NPs exposure decreased the abundance of ARGs. Furthermore, the co-exposure of Cu- and ZnO- NPs induced obvious changes in the microbial communities compared to the control communities. Redundancy analysis suggested that the microbial community contributed the most (43.5%) to the ARG profiles, followed by dissolved metal ions (25.7%), MRGs, (19.4%), and MGEs (4.4%). Network analysis found several potential hosts (such as Mycobacterium and Escherichia coli ) and implied the extent of the risk of ARG transmission into various environmental niches by these common microbes.

Proteomic profiling reveals dysregulated mitochondrial complex subunits responsible for myocardial toxicity induced by SiNPs - Xinying Zhao; Hailin Xu; Yan Li; Ru Ma; Yi Qi; Min Zhang; Caixia Guo; Zhiwei Sun; Yanbo Li (Science of The Total Environment, 2023)

Quinone redox cycling drives lignocellulose depolymerization and degradation in composting environments based on metagenomics analysis - Ru Sun; Ziyi Cao; Xiaoli Wen; Liangcai Ma; Yucheng Zhou; Jixuan Li; Mengxin Fu; Pengfei Zhu; Kecheng Li; Qunliang Li (Science of The Total Environment, 2023)

Lycopsid Lepacyclotes Emmons from the Middle Triassic of the Ordos Basin, North China and reviews of the genus - Shenghui Deng; Yuanzheng Lu; Ru Fan; Zhong Luo; Xueying Ma; Dan Lyu; Yanqi Sun (Review of Palaeobotany and Palynology, 2023)

Citric acid-based deep eutectic solvent (CA-DES) as a new soil detergent for the removal of cadmium from coking sites - Jie Qian; Ying-hua Li; Fei Su; Ji-guo Wu; Jia-ru Sun; Tian-ci Huang (Environmental Science and Pollution Research, 2023)

Silencing RPL8 inhibits the progression of hepatocellular carcinoma by down-regulating the mTORC1 signalling pathway - Tao Sun; Weiying Zhu; Qingjing Ru; Yi Zheng (Human Cell, 2022)

Recent advances in biotechnological production of polyunsaturated fatty acids by Yarrowia lipolytica - Yu-Lei Jia; Ling-Ru Wang; Zi-Xu Zhang; Yang Gu; Xiao-Man Sun (Critical Reviews in Food Science and Nutrition, 2022)

The impact of low-carbon city pilot policy on green total-factor productivity in China’s cities - Ke-Liang Wang; Jin Li; Ru-Yu Xu; Su-Qin Pang; Zhuang Miao; Hua-Ping Sun (Environmental Science and Pollution Research, 2022)

Seasonal variations in microbial diversity and metabolite profiles of the gut of sea cucumber (Apostichopus japonicus) - Beini Deng; Xiaoshang Ru; Ting Wang; Chenxi Zhang; Wanhui Sun; Songchong Lu; Libin Zhang (Frontiers in Marine Science, 2022)
The sea cucumber ( Apostichopus japonicus ) is the main economic species in China and has a significant role in aquaculture. Gut microbiome composition is closely related to external environments. In this study, we identified the effects of seasonal changes on the composition and main metabolites of symbiotic microorganisms in the intestine of A. japonicus . We used 16S rRNA sequencing to identify the composition of symbiotic microorganisms in different seasons. Intestinal metabolites were determined using liquid chromatography with tandem mass spectrometry, which linked symbiotic microorganisms to intestinal metabolites. Analyzing changes in intestinal microbial composition across different seasons. The results showed that seasonal changes of intestinal microorganisms were significant, A. japonicus were infected by Vibrio easily in summer, Stigmasterol and sitosterol could affect the growth of body wall of A. japonicus . It is vital importance for A. japonicus that the results benefit for the growth, immunity and aquaculture.

Involvement of osmoregulation, glyoxalase, and non-glyoxalase systems in signaling molecule glutamic acid-boosted thermotolerance in maize seedlings - Xue-Mei Qiu; Yu-Ying Sun; Jia-Qi Wang; Ru-Hua Xiang; Zhong-Guang Li (Protoplasma, 2022)

ACOT7 protects epidermal stem cells against lipid peroxidation - Guang Zhang; Jiaxu Ma; Zhenjie Wu; Guoqi Cao; Chunyan Liu; Ru Song; Rui Sun; Aoyu Chen; Yibing Wang; Siyuan Yin (In Vitro Cellular & Developmental Biology - Animal, 2022)
Epidermal stem cells (ESCs) are critical for skin regeneration and repair. Previous studies have shown that ESCs are susceptible to oxidative stress, which in turn leads to lipid peroxidation and affects skin repair. Our study aims to explore how ESCs resist lipid peroxidation. By performing proteomics analysis, we found that the expression of Acyl-CoA thioesterase 7 (ACOT7) was positively correlated with the concentration of transferrin. Overexpression adenovirus vectors of ACOT7 were constructed and transfected into ESCs. Levels of lipid peroxidation by flow cytometry, cell viabilities, and MDA levels were measured. The results revealed that ACOT7 could inhibit lipid peroxidation, reduce the level of malondialdehyde (MDA), and improve the survival rate of ESCs induced by H 2 O 2 , Erastin, and RSL3. Our data suggest that ACOT7 has an effect on protecting ESCs against iron-dependent lipid peroxidation.

Traffic noise and adiposity: a systematic review and meta-analysis of epidemiological studies - Si-Yu Gui; Ke-Jia Wu; Yue Sun; Yue-Nan Chen; Huan-Ru Liang; Wen Liu; Yao Lu; Cheng-Yang Hu (Environmental Science and Pollution Research, 2022)

Microbial composition and nitrogen removal pathways in a novel sequencing batch reactor integrated with semi-fixed biofilm carrier: evidence from a pilot study for low- and high-strength sewage treatment - Peng-fei Chen; Rui-jian Zhang; Zhi-li Du; Guang-hua Wang; Hao-tao Dong; Bin Cui; Ru-pei Fan; Lu-xin Li; Qian-bin Wang; Ying-shi Liu; Zhi-min Sun (Environmental Science and Pollution Research, 2022)

Surrogate production of genome-edited sperm from a different subfamily by spermatogonial stem cell transplantation - Fenghua Zhang; Yongkang Hao; Xianmei Li; Yi Li; Ding Ye; Ru Zhang; Xiaosi Wang; Mudan He; Houpeng Wang; Zuoyan Zhu; Yonghua Sun (Science China Life Sciences, 2022)

First report of Capsicum frutescens endornavirus 1 infecting pepper in China - Ming-xia Gong; Hu Zhao; Xing Wu; Meng Wang; Zeng-jing Zhao; Zhi He; Ru-kui Huang; Jing-ping Sun; Ri-sheng Wang (Journal of Plant Pathology, 2022)

Imatinib-induced hepatotoxicity via oxidative stress and activation of NLRP3 inflammasome: an in vitro and in vivo study - Feng-Ru Huang; Wen-Tong Fang; Zi-Ping Cheng; Ye Shen; Dun-Jian Wang; Yong-Qing Wang; Lu-Ning Sun (Archives of Toxicology, 2022)

Using potassium ferrate control hazardous disinfection by-products during chlorination - Mei Li; Jing Sun; Dan Dan Wang; Ru Zhang; Hongbo Wang; Ning Wang (Environmental Science and Pollution Research, 2021)

Marinifaba aquimaris gen. nov., sp. nov., a novel chitin‐degrading gammaproteobacterium in the family Alteromonadaceae isolated from seawater of the Mariana Trench - Xin Sui; Xiao-yan He; Ning-hua Liu; Yan-ru Dang; Qian-qian Cha; Mei-ling Sun; Chun-yang Li; Hui-hui Fu; Xiao-yan Song; Qi-long Qin; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

New 40Ar/39Ar and (U-Th)/He dating for the Zhunuo porphyry Cu deposit, Gangdese belt, southern Tibet: implications for pulsed magmatic-hydrothermal processes and ore exhumation and preservation - Xiang Sun; Cheng-Biao Leng; Pete Hollings; Qing-Jie Song; Ru-Yue Li; Xiu-Quan Wan (Mineralium Deposita, 2021)

The Knowledge and Attitude Towards Advance Care Planning Among Chinese Patients with Advanced Cancer - Xiao-Ting Hou; Yu-Han Lu; Hong Yang; Ren-Xiu Guo; Yun Wang; Li-Hong Wen; Ya-Ru Zhang; Hong-Yu Sun (Journal of Cancer Education, 2021)

A rapid and accurate method for identifying sexuality of Indarbela obliquifasciata Mell (Lepidoptera, Metarbelidae) adults and pupae - Li-Zhi Huo; Long-Hua Sun; Jing-Ai Zhang; Chao Wu; Ya-Hui Hou; Yong-Yue Wang; Zhi-Jie Li; Jia-Ru Deng; Si-Meng Yang; Ke-Ke Bi (International Journal of Tropical Insect Science, 2021)

Double Weighted Sparse Nonnegative Tensor Factorization for Hyperspectral Unmixing - Heng-Chao Li; Shuang Liu; Xin-Ru Feng; Rui Wang; Yong-Jian Sun (International Journal of Remote Sensing, 2021)

Experimental evidence for long‐term coexistence of copiotrophic and oligotrophic bacteria in pelagic surface seawater - Yi Li; Zhi‐Bin Wang; Xi‐Ying Zhang; Yan‐Ru Dang; Lin‐Lin Sun; Wei‐Peng Zhang; Hui‐Hui Fu; Gui‐Peng Yang; Min Wang; Andrew McMinn; Xiu‐Lan Chen; Yin Chen; et al. (Environmental Microbiology, 2021)
Summary Most marine copiotrophic bacteria can produce extracellular enzymes to degrade biopolymers into bio‐available smaller solutes, while oligotrophic bacteria usually cannot. Bacterial extracellular enzymes and enzymatic products can be a common resource that could be utilized by both copiotrophs and oligotrophs; when present, oligotrophs may outcompete the enzyme‐producing copiotrophs. However, copiotrophs and oligotrophs consistently coexist in the ocean. How they maintain coexistence has still not been experimentally studied. In this study, the interaction and coexistence of a copiotroph and an oligotroph, isolated from the same surface seawater sample and utilizing the same proteinaceous substrate, were experimentally investigated. The copiotroph could secrete extracellular proteases to degrade and then utilize the proteinaceous substrate. The oligotroph was unable to utilize the proteinaceous substrate by itself, but could grow by using the hydrolysate amino acids. The copiotroph outcompeted the oligotroph by adsorbing the amino acids quickly and having a higher growth rate in the rich medium. The oligotroph survived by adapting to low concentration of nutrients. The copiotroph and oligotroph were able to maintain long‐term (up to 142 days) coexistence in the laboratory. This study indicates that differences in the utilization of different concentrations of nutrients can drive the coexistence of marine copiotrophs and oligotrophs.

Application and Progress of Reinforcement Technology for Chinese Ancient Buildings with Wood Structure - Ru-yuan Yang; You-fu Sun; Xiao-feng Zhang (Geotechnical and Geological Engineering, 2020)

FW0622, a new siderophore isolated from marine Verrucosispora sp. by genomic mining - Wei Zhao; Fei Peng; Chuan-xi Wang; Yang Xie; Ru Lin; Zhi-kai Fang; Fei Sun; Yun-yang Lian; Hong Jiang (Natural Product Research, 2020)

Low Serum Uric Acid Levels Promote Hypertensive Intracerebral Hemorrhage by Disrupting the Smooth Muscle Cell-Elastin Contractile Unit and Upregulating the Erk1/2-MMP Axis - Ning Xiao; Tian-long Liu; Hao Li; Hao-chen Xu; Jing Ge; Hong-yan Wen; Cong-xia Bai; Li Song; Ying-ying Sun; Yin-hui Zhang; Ru-tai Hui; Wei-hua Song; et al. (Translational Stroke Research, 2020)

Prenatal di-(2-ethylhexyl) phthalate maternal exposure impairs the spatial memory of adult mouse offspring in a phase- and gender-dependent manner - Ling-Li Zhao; Ru Shen; Cong-Cong Sun; Shan-Yu Zhang; Bo Wang; Mei-Fang Sun; De-Xiang Xu (Environmental Science and Pollution Research, 2020)

LncRNAs and circular RNAs as endothelial cell messengers in hypertension: mechanism insights and therapeutic potential - Ji-Ru Zhang; Hai-Jian Sun (Molecular Biology Reports, 2020)

Enhanced Antitumor Efficacy of Curcumin-Loaded PLGA Nanoparticles Coated with Unique Fungal Hydrophobin - Lu Sun; Hui Xu; Jing-hua Xu; Shao-ning Wang; Jun-wei Wang; Hong-feng Zhang; Wei-ru Jia; Lin-sen Li (AAPS PharmSciTech, 2020)

Occurrence and distribution of priority pharmaceuticals in the Yellow River and the Huai River in Henan, China - Jinglan Feng; Qi Liu; Xiangli Ru; Nannan Xi; Jianhui Sun (Environmental Science and Pollution Research, 2020)

Tumor promoting effects of glucagon receptor: a promising biomarker of papillary thyroid carcinoma via regulating EMT and P38/ERK pathways - Hong-Chun Jiang; Xiang-Ru Chen; Hai-Feng Sun; Yuan-Wen Nie (Human Cell, 2020)

Development of Human in vitro Brain-blood Barrier Model from Induced Pluripotent Stem Cell-derived Endothelial Cells to Predict the in vivo Permeability of Drugs - Yuan Li; Xueying Sun; Houfu Liu; Liang Huang; Guofeng Meng; Yu Ding; Wenji Su; Jiaqi Lu; Sophie Gong; Georg C. Terstappen; Ru Zhang; Wandong Zhang (Neuroscience Bulletin, 2019)

Upregulation of proBDNF in the Mesenteric Lymph Nodes in Septic Mice - Zhe Wang; Jia-Li Wu; Feng Zhong; Yu Liu; Yun-Qing Yu; Jing-Jing Sun; Shuang Wang; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2019)

Innovation-based urbanization: Evidence from 270 cities at the prefecture level or above in China - Lachang Lyu; Feixiang Sun; Ru Huang (Journal of Geographical Sciences, 2019)

Exogenous application of gibberellic acid and ascorbic acid improved tolerance of okra seedlings to NaCl stress - Yong-Hui Wang; Gen Zhang; Yuan Chen; Jin Gao; Yan-Ru Sun; Ming-Fa Sun; Jian-Ping Chen (Acta Physiologiae Plantarum, 2019)

Geomorphic features of Quaternary glaciation in the Taniantaweng Mountain, on the southeastern Qinghai-Tibet Plateau - Wei Zhang; Le Chai; Ian S Evans; Liang Liu; Ya-peng Li; Jing-ru Qiao; Qian-yu Tang; Bo Sun (Journal of Mountain Science, 2019)

Transplantation of UC-MSCs on collagen scaffold activates follicles in dormant ovaries of POF patients with long history of infertility - Lijun Ding; Guijun Yan; Bin Wang; Lu Xu; Yan Gu; Tong Ru; Xiaoying Cui; Lei Lei; Jingyu Liu; Xiaoqiang Sheng; Bin Wang; Chunxue Zhang; et al. (Science China Life Sciences, 2018)

Population genomic analysis reveals that homoploid hybrid speciation can be a lengthy process - Dafu Ru; Yongshuai Sun; Donglei Wang; Yang Chen; Tianjing Wang; Quanjun Hu; Richard J. Abbott; Jianquan Liu (Molecular Ecology, 2018)
An increasing number of species are thought to have originated by homoploid hybrid speciation ( HHS ), but in only a handful of cases are details of the process known. A previous study indicated that Picea purpurea , a conifer in the Qinghai–Tibet Plateau ( QTP ), originated through HHS from P. likiangensis and P. wilsonii . To investigate this origin in more detail, we analysed transcriptome data for 114 individuals collected from 34 populations of the three Picea species from their core distributions in the QTP . Phylogenetic, principal component and admixture analyses of nuclear SNP s showed the species to be delimited genetically and that P. purpurea was admixed with approximately 60% of its ancestry derived from P. wilsonii and 40% from P. likiangensis . Coalescent simulations revealed the best‐fitting model of origin involved formation of an intermediate hybrid lineage between P. likiangensis and P. wilsonii approximately 6 million years ago (mya), which backcrossed to P. wilsonii to form P. purpurea approximately one mya. The intermediate hybrid lineage no longer exists and is referred to as a “ghost” lineage. Our study emphasizes the power of population genomic analysis combined with coalescent analysis for reconstructing the stages involved in the origin of a homoploid hybrid species over an extended period. In contrast to other studies, we show that these stages can in some instances span a relatively long period of evolutionary time.

Efficient generation of functional cardiomyocytes from human umbilical cord-derived virus-free induced pluripotent stem cells - Kai Hong Wu; Su Yun Wang; Qian Ru Xiao; Yu Yang; Ning Ping Huang; Xu Ming Mo; Jian Sun (Cell and Tissue Research, 2018)

An optimized fed-batch culture strategy integrated with a one-step fermentation improves l-lactic acid production by Rhizopus oryzae - Yongqian Fu; Xiaolong Sun; Huayue Zhu; Ru Jiang; Xi Luo; Longfei Yin (World Journal of Microbiology and Biotechnology, 2018)

Ectopic expression of sorbitol-6-phosphate 2-dehydrogenase gene from Haloarcula marismortui enhances salt tolerance in transgenic Arabidopsis thaliana - Jian-jie Gao; Yu-ru Sun; Bo Zhu; Ri-He Peng; Bo Wang; Li-Juan Wang; Zhen-Jun Li; Lei Chen; Quan-Hong Yao (Acta Physiologiae Plantarum, 2018)

Echinacoside, a phenylethanoid glycoside from Cistanche deserticola, extends lifespan of Caenorhabditis elegans and protects from Aβ-induced toxicity - Wei Chen; Hong-Ru Lin; Cong-Min Wei; Xiao-Hua Luo; Meng-Lu Sun; Zhen-Zhou Yang; Xin-Yan Chen; Hong-Bing Wang (Biogerontology, 2018)

Metabolic benefits of rivaroxaban in non-valvular atrial fibrillation patients after radiofrequency catheter ablation - Jun Zhu; Rong-jun Gao; Qiang Liu; Ru-hong Jiang; Lu Yu; Ya-xun Sun; Pei Zhang; Jian-wei Lin; Yang Ye; Zu-wen Zhang; Shi-quan Chen; Hui Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Erratum to: Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

Characteristic differences in essential oil composition of six Zanthoxylum bungeanum Maxim. (Rutaceae) cultivars and their biological significance - Shu-ming Liu; Shi-jun Wang; Si-yao Song; Yong Zou; Jun-ru Wang; Bing-yin Sun (Journal of Zhejiang University-SCIENCE B, 2017)

Repeated Neonatal Sevoflurane Exposure-Induced Developmental Delays of Parvalbumin Interneurons and Cognitive Impairments Are Reversed by Environmental Enrichment - Mu-huo Ji; Zhong-yun Wang; Xiao-ru Sun; Hui Tang; Hui Zhang; Min Jia; Li-li Qiu; Guang-fen Zhang; Yong G. Peng; Jian-jun Yang (Molecular Neurobiology, 2017)

Effects of xeric shrubs on soil microbial communities in a desert in northern China - Yanfei Sun; Yuqing Zhang; Wei Feng; Shugao Qin; Zhen Liu; Yuxuan Bai; Ru Yan; Keyu Fa (Plant and Soil, 2017)

Reversible Absorption and Emission Responses of Nile Blue and Azure A Derivatives in Extreme Acidic and Basic Conditions - Xiu-Li Wang; Ru Sun; Wei-Jin Zhu; Xin-Long Sha; Jian-Feng Ge (Journal of Fluorescence, 2017)

Transplantation of collagen scaffold with autologous bone marrow mononuclear cells promotes functional endometrium reconstruction via downregulating ΔNp63 expression in Asherman’s syndrome - Guangfeng Zhao; Yun Cao; Xianghong Zhu; Xiaoqiu Tang; Lijun Ding; Haixiang Sun; Juan Li; Xinan Li; Chenyan Dai; Tong Ru; Hui Zhu; Jingjie Lu; et al. (Science China Life Sciences, 2017)

Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

NOX2 Mediated-Parvalbumin Interneuron Loss Might Contribute to Anxiety-Like and Enhanced Fear Learning Behavior in a Rat Model of Post-Traumatic Stress Disorder - Fang-fang Liu; Lin-dong Yang; Xiao-ru Sun; Hui Zhang; Wei Pan; Xing-ming Wang; Jian-jun Yang; Mu-huo Ji; Hong-mei Yuan (Molecular Neurobiology, 2016)

Reactive Oxygen Species-mediated Loss of Phenotype of Parvalbumin Interneurons Contributes to Long-term Cognitive Impairments After Repeated Neonatal Ketamine Exposures - Hui Zhang; Xiao-ru Sun; Jing Wang; Zhen-zhen Zhang; Hong-ting Zhao; Hui-hui Li; Mu-huo Ji; Kuan-yu Li; Jian-jun Yang (Neurotoxicity Research, 2016)

Trans-cinnamaldehyde protected PC12 cells against oxygen and glucose deprivation/reperfusion (OGD/R)-induced injury via anti-apoptosis and anti-oxidative stress - Xue Qi; Ru Zhou; Yue Liu; Jing Wang; Wan-Nian Zhang; Huan-Ran Tan; Yang Niu; Tao Sun; Yu-Xiang Li; Jian-Qiang Yu (Molecular and Cellular Biochemistry, 2016)

Molecular Design, Structural Analysis and Antifungal Activity of Derivatives of Peptide CGA-N46 - Rui-Fang Li; Zhi-Fang Lu; Ya-Nan Sun; Shi-Hua Chen; Yan-Jie Yi; Hui-Ru Zhang; Shuo-Ye Yang; Guang-Hai Yu; Liang Huang; Chao-Nan Li (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Molecular characterization of two divergent variants of sugarcane bacilliform viruses infecting sugarcane in China - Sheng-Ren Sun; Mona B. Damaj; Olufemi J. Alabi; Xiao-Bin Wu; T. Erik Mirkov; Hua-Ying Fu; Ru-Kai Chen; San-Ji Gao (European Journal of Plant Pathology, 2016)

Genomic variability and molecular evolution of Asian isolates of sugarcane streak mosaic virus - Shan-Shan Liang; Olufemi J. Alabi; Mona B. Damaj; Wei-Lin Fu; Sheng-Ren Sun; Hua-Ying Fu; Ru-Kai Chen; T. Erik Mirkov; San-Ji Gao (Archives of Virology, 2016)

Genomic evidence for polyphyletic origins and interlineage gene flow within complex taxa: a case study of Picea brachytyla in the Qinghai‐Tibet Plateau - Dafu Ru; Kangshan Mao; Lei Zhang; Xiaojuan Wang; Zhiqiang Lu; Yongshuai Sun (Molecular Ecology, 2016)
Hybridization and introgression are believed to play important roles in plant evolution. However, few empirical studies have been designed to clarify the ways in which these processes complicate taxonomic delimitation. Recent phylogenetic studies based on a number of different DNA fragments have indicated that Picea brachytyla in the eastern Qinghai‐Tibet Plateau is polyphyletic, a finding that contrasts with traditional taxonomy based on morphological traits. We aimed to test this conflict using transcriptomic data from 26 trees collected from multiple localities for this and related species. Our phylogenomic analyses suggest that the sampled trees of P. brachytyla cluster into two distinct lineages corresponding to the two taxonomically recognized intraspecific varieties: var. brachytyla and var. complanata . However, var. complanata nested within Picea likiangensis and was sister to one of its three varieties, while var. brachytyla comprised an isolated lineage. The polyphyletic origin hypothesis was further supported by likelihood tree comparisons using Akaike's information criterion (AIC) and by coalescent analyses under the snapp model. However, our abba‐baba and ∂a∂i analyses suggest that gene flow between these two independently evolved lineages has been extensive and bidirectional. Introgression, as well as parallel evolution in the arid habitats common to both lineages, may have given rise to their morphological similarity. Our study highlights the importance of genomic evidence and the use of newly developed coalescent analysis methods for clarifying the evolutionary complexity of certain plant taxa.

Effect of desiccation in shade on in vitro oocyte maturation and development of the sea cucumber Apostichopus japonicus (Echinodermata: Holothuroidea) - Shilin Liu; Yi Zhou; Tao Zhang; Lina Sun; Xiaoshang Ru; Junhua Li; Hongsheng Yang (Invertebrate Reproduction & Development, 2016)

Hypermethylation of Hippocampal Synaptic Plasticity-Related genes is Involved in Neonatal Sevoflurane Exposure-Induced Cognitive Impairments in Rats - Ling-sha Ju; Min Jia; Jie Sun; Xiao-ru Sun; Hui Zhang; Mu-huo Ji; Jian-jun Yang; Zhong-yun Wang (Neurotoxicity Research, 2016)

Low-Dose Topical 5-Aminolevulinic Acid Photodynamic Therapy in the Treatment of Different Severity of Acne Vulgaris - Shi-qin Tao; Fei Li; Lei Cao; Ru-shan Xia; Hua Fan; Ying Fan; Hui Sun; Cheng Jing; Li-jia Yang (Cell Biochemistry and Biophysics, 2015)

Environmental Enrichment Ameliorates Neonatal Sevoflurane Exposure-Induced Cognitive and Synaptic Plasticity Impairments - Mu-huo Ji; Xing-ming Wang; Xiao-ru Sun; Hui Zhang; Ling-sha Ju; Li-li Qiu; Jiao-jiao Yang; Min Jia; Jing Wu; Jianjun Yang (Journal of Molecular Neuroscience, 2015)

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

Association between vitamin D receptor gene polymorphism (TaqI) and obesity in Chinese population - HUI-RU FAN; LI-QUN LIN; HAO MA; YING LI; CHANG-HAO SUN (Journal of Genetics, 2015)

Exosomes from Dendritic Cells Loaded with Chaperone-Rich Cell Lysates Elicit a Potent T Cell Immune Response Against Intracranial Glioma in Mice - Ning Bu; Haiqin Wu; Guilian Zhang; Shuqin Zhan; Ru Zhang; Hong Sun; Yun Du; Li Yao; Huqing Wang (Journal of Molecular Neuroscience, 2015)

Two new triterpenoids from Nauclea officinalis - Hai-Yang Wang; Ke Liu; Ru-Xia Wang; San-Hai Qin; Feng-Ling Wang; Jing-Yong Sun (Natural Product Research, 2015)

Distribution and ecological risk assessment of HCHs and DDTs in surface seawater and sediment of the mariculture area of Jincheng Bay, China - Yanbing Hu; Shan Sun; Xiukai Song; Jianxin Ma; Shaoguo Ru (Journal of Ocean University of China, 2015)

Augmenter of liver regeneration plays a protective role against hydrogen peroxide-induced oxidative stress in renal proximal tubule cells - Ning Xia; Ru-yu Yan; Qi Liu; Xiao-hui Liao; Hang Sun; Hui Guo; Ling Zhang (Apoptosis, 2015)

The Recovery Process of Mice Tracheal Epithelium Injured by 5-FU and Its Microarray Analysis - Jing-Ru Zhang; Nan Song; Xin-Shan Jia; Shan-Liang Sun; Xiao-Bo Ma; En-Hua Wang (Cell Biochemistry and Biophysics, 2014)

Non-pulmonary vein foci induced before and after pulmonary vein isolation in patients undergoing ablation therapy for paroxysmal atrial fibrillation: incidence and clinical outcome - Hui Cheng; Yin-yin Dai; Ru-hong Jiang; Qiang Liu; Ya-xun Sun; Jian-wei Lin; Zu-wen Zhang; Shi-quan Chen; Jun Zhu; Xia Sheng; Chen-yang Jiang (Journal of Zhejiang University-SCIENCE B, 2014)

Metabolomic approach to optimizing and evaluating antibiotic treatment in the axenic culture of cyanobacterium Nostoc flagelliforme - Pei-pei Han; Shi-ru Jia; Ying Sun; Zhi-lei Tan; Cheng Zhong; Yu-jie Dai; Ning Tan; Shi-gang Shen (World Journal of Microbiology and Biotechnology, 2014)

SNP and haplotype analysis reveal IGF2 variants associated with growth traits in Chinese Qinchuan cattle - Yong-Zhen Huang; Zhao-Yang Zhan; Xin-Yi Li; Sheng-Ru Wu; Yu-Jia Sun; Jing Xue; Xian-Yong Lan; Chu-Zhao Lei; Chun-Lei Zhang; Yu-Tang Jia; Hong Chen (Molecular Biology Reports, 2014)

Circulating microparticles in patients with coronary heart disease and its correlation with interleukin-6 and C-reactive protein - Ying Cui; Lihui Zheng; Ming Jiang; Ru Jia; Xiao Zhang; Qishan Quan; Guiqin Du; Dongjin Shen; Xiaodan Zhao; Wenying Sun; Hongwei Xu; Lijuan Huang (Molecular Biology Reports, 2013)

Occurrence of rust of Sophora flavescens caused by Uromyces sophorae-flavescentis in China - Ru-Jun Zhou; Jun-Fan Fu; Ning Hao; Zhen Liu; Ying Sun (Phytoparasitica, 2013)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Edaravone Ameliorates Oxidative Damage Associated with Aβ25-35 Treatment in PC12 Cells - Gui-lian Zhang; Wang-gang Zhang; Yun Du; Li Yao; Hong Sun; Ru Zhang; Enqi Liu; Ning Bu; Hai-qin Wu; Lei Zhang; Ting-ting Li; Ying-ying Guo (Journal of Molecular Neuroscience, 2013)

Toxicokinetics of tilapia following high exposure to waterborne and dietary copper and implications for coping mechanisms - Jeng-Wei Tsai; Yun-Ru Ju; Ying-Hsuan Huang; Yue-Sun Deng; Wei-Yu Chen; Chin-Ching Wu; Chung-Min Liao (Environmental Science and Pollution Research, 2013)

Protective effect of hydrogen-rich saline on ischemia/reperfusion injury in rat skin flap - Ling Zhao; You-bin Wang; Shi-rui Qin; Xue-mei Ma; Xue-jun Sun; Ming-lian Wang; Ru-gang Zhong (Journal of Zhejiang University-SCIENCE B, 2013)

Analysis of B-Class Genes NAP3L3 and NAP3L4 in Narcissus tazetta var. chinensis - Xiao-Fang Li; Jing Xu; Ru Yang; Lin-Yan Jia; Xin-Jie Deng; Li-Jun Xiong; Xue-Ping Zhang; Qi Fang; Wei Zhang; Yue Sun; Ling Xu (Plant Molecular Biology Reporter, 2013)

Spatio-temporal variation of landscape heterogeneity under influence of human activities in Xiamen City of China in recent decade - Yixiong Huang; Xiuqin Yin; Gongfu Ye; Jiemin Lin; Ru Huang; Na Wang; Liang Wang; Yue Sun (Chinese Geographical Science, 2013)

Expression, purification, and evaluation for anticancer activity of ribosomal protein L31 gene (RPL31) from the giant panda (Ailuropoda melanoleuca) - Xiu-Lan Su; Yi-Ling Hou; Xiang-Hui Yan; Xiang Ding; Wan-Ru Hou; Bing Sun; Si-Nan Zhang (Molecular Biology Reports, 2012)

Culture-independent characterization of the autochthonous gut microbiota of grouper Epinephelus coioides following the administration of probiotic Enterococcus faecium - Yun-Zhang Sun; Hong-Ling Yang; Ru-Long Ma; Kun-Peng Huang; Ji-Dan Ye (Aquaculture International, 2012)

Molecular characterization and expression analysis of elongation factors 1A and 2 from the Pacific white shrimp, Litopenaeus vannamei - Lei Wang; Yuan Liu; Wei-Na Wang; Wei-Jun Mai; Yu Xin; Jun Zhou; Wen-Yin He; An-Li Wang; Ru-Yong Sun (Molecular Biology Reports, 2011)

Proteomic survey towards the tissue-specific proteins of mouse mitochondria - Yuan Wang; HaiDan Sun; YaWei Ru; SongYue Yin; Liang Yin; SiQi Liu (Science China Life Sciences, 2011)

Simulation of organic carbon dynamics at regional scale for paddy soils in China - Xue-Zheng Shi; Ru-Wei Yang; David C. Weindorf; Hong-Jie Wang; Dong-Sheng Yu; Yao Huang; Xian-Zhang Pan; Wei-Xia Sun; Li-Ming Zhang (Climatic Change, 2010)

Origin of the Gangdise (Transhimalaya) Permian arc in southern Tibet: Stratigraphic and volcanic geochemical constraints - Quan‐Ru Geng; Zhi‐Ming Sun; Gui‐Tang Pan; Di‐Cheng Zhu; Li‐Quan Wang (Island Arc, 2009)
The well‐studied Mesozoic and Cenozoic volcanic rocks of the Gangdise Terrane, southern Tibet, are widely interpreted to have resulted from subduction of the Neotethys; however, Late Paleozoic volcanic rocks and their tectonic setting remain poorly studied. Based on new geological data, we carried out stratigraphical and geochemical analyses of Permian volcano‐stratigraphic sequences within an east–west‐trending, fault‐bounded zone of uplift in the central Gangdise Terrane. Sedimentary rocks in this area consist of platform carbonates and terrigenous clastic rocks that represent widespread shallow‐marine sedimentary basins developed around northern Gondwana. A regression or tectonic uplift event is recorded in Permian sedimentary rocks that show the local development of fluvial environments. The sedimentary succession contains evidence of two volcanic stages: a period of basaltic extrusions and younger explosive felsic magmatism. The first volcanic stage is Early and Middle Permian in age. Tholeiitic basaltic lavas are exposed around Maizhokunggar (Tangjia) and Lhunzhub in central Gangdise. The Lower Permian basalts are relatively enriched in MgO (4.58–12.19%), whereas the Middle Permian basalts are characterized by high Al 2 O 3 contents (11.75–21.22%). Rocks of both ages are enriched in large‐ion lithophile elements (LILE) and light rare earth elements (LREE), and show pronounced negative Nb and Ta anomalies. Total REE contents and light (LREE)/heavy (HREE) ratios increased from the Early to Middle Permian. Observed variations in initial Sr, Nd, and Pb isotopes ( 87 Sr/ 86 Sr i = 0.7013–0.7066, 207 Pb/ 204 Pb i = 15.53–15.63, and 208 Pb/ 204 Pb i = 38.04–38.64 for a given 206 Pb/ 204 Pb i ; εNd = +0.69 to −11.55) can be explained by crustal interaction with mantle sources, as is characteristic of metasomatism by slab‐derived fluids or assimilation and fractional crystallization (AFC) processes during magmatic evolution. The observed geochemical signatures, coupled with stratigraphic constraints, support the hypothesis that an initial arc formed during the Permian due to southward subduction of the Paleotethys, predating the well‐known Mesozoic arc preserved in the Gangdise Terrane.

Human mesenchymal stem cells-like cells as cellular vehicles for delivery of immunotoxin in vitro - Chang-chen Hu; Yi-quan Ke; Xin-lin Sun; Xiao-dan Jiang; Ru-xiang Xu; Jun Lv; Yu-sheng Wang; Ying-qian Cai; Ling-sha Qin; Yu-xi Zou (Biotechnology Letters, 2009)

A new labdane-type diterpene from the bark of Juniperus chinensis Linn. - Chi-I Chang; Wen-Ching Chen; Yi-Yuan Shao; Guey-Ru Yeh; Ning-Sun Yang; Wenchang Chiang; Yueh-Hsiung Kuo (Natural Product Research, 2008)

A rapid accurate culture assay for infectivity in Transmissible Encephalopathies - Ying Liu; Ru Sun; Trisha Chakrabarty; Laura Manuelidis (Journal of NeuroVirology, 2008)

Application of Bayesian Regularized BP Neural Network Model for Trend Analysis, Acidity and Chemical Composition of Precipitation in North Carolina - Min Xu; Guangming Zeng; Xinyi Xu; Guohe Huang; Ru Jiang; Wei Sun (Water, Air, & Soil Pollution, 2006)

TransgenicLycium barbarum L. Established as HIV capsid protein expression system - Guo-Li Du; Chang-Zheng Song; Geng-Lin Zhang; Xiao-Guang Sun; Dan-Ru Liu (Plant Molecular Biology Reporter, 2005)

The effects of vitamin E on non-specific immune response of the juvenile soft-shelled turtle Pelodiscus sinensis - Xian-Qing ZHOU; Cui-Juan NIU; Ru-Yong SUN (Fisheries Science, 2005)

Maternal lineages of Pinus densata , a diploid hybrid - Bao‐Hua Song; Xiao‐Quan Wang; Xiao‐Ru Wang; Lan‐Ju Sun; De‐Yuan Hong; Pei‐Hao Peng (Molecular Ecology, 2002)
Previous morphological, allozyme and chloroplast DNA data have suggested that Pinus densata originated through hybridization between P . tabuliformi s and P . yunnanensis . In the present study, sequence and restriction site analyses of maternally inherited mitochondrial nad 1 intron were used to detect variation patterns in 19 populations of P . tabuliformis , P . yunnanensis and P . densata . A total of three mitotypes (A, B, C) were detected. All but one of the populations of P . yunnanensis possessed mitotype B while all populations of P . tabuliformis had mitotype A. Pinus densata populations, on the other hand, harboured both mitotypes A and B, which are characteristic of P . tabuliformis and P . yunnanensis , respectively . This result gives strong additional evidence supporting the hybrid origin of this diploid pine. The distribution of mitotypes indicated very different mating compositions and evolutionary history among P . densata populations. It seems that local founder populations and backcrosses may have played important roles in the early establishment of P . densata populations. The uplift of the Tibetan Plateau had a significant impact on the distribution of maternal lineages of P . densata populations.